Lithium-based solid electrolyte, method for producing lithium-based solid electrolyte, modified positive electrode active material, modified negative electrode active material, all-solid secondary battery, electrode sheet for all-
By preparing a lithium-based solid electrolyte containing amorphous lithium tetraborate, water, and lithium salt, the safety and space limitations of liquid electrolytes were solved, and a high-conductivity all-solid-state secondary battery was realized.
Patent Information
- Application Number
- CN202380043016.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-11-08
- Filing Date
- 2023-05-26
- Publication Date
- 2025-01-07
AI Technical Summary
Existing lithium-ion secondary batteries suffer from issues related to the flammability and space constraints of liquid electrolytes, and their conductivity needs improvement.
A lithium-based solid electrolyte containing amorphous lithium tetraborate, water, and lithium salt is prepared through mechanical grinding and drying processes to form mesh-like lithium salt regions to improve ion conductivity.
A lithium-based solid electrolyte with excellent ion conductivity has been developed, which improves the safety and capacity of the battery and is suitable for all-solid-state rechargeable batteries.
Smart Images

Figure CN119278527A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a lithium-based solid electrolyte, a method for producing a lithium-based solid electrolyte, a modified positive electrode active material, a modified negative electrode active material, an all-solid-state secondary battery, an electrode sheet for an all-solid-state secondary battery, a solid electrolyte sheet, and an electrode for an all-solid-state secondary battery. Background Art
[0002] In the past, liquid electrolytes with high ion conductivity have been used in lithium-ion secondary batteries. However, since liquid electrolytes are flammable, there are safety issues. In addition, since they are in a liquid state, it is difficult to make them compact, and when the battery becomes larger, the capacity limitation also becomes a problem.
[0003] In contrast, all-solid-state lithium-ion secondary batteries are one of the next-generation batteries that can solve these problems. In all-solid-state batteries, in order to obtain the desired charge and discharge characteristics, a solid electrolyte with good ion conductivity is required. For example, Patent Document 1 discloses a solid electrolyte based on an oxide containing lithium that can be used in all-solid-state lithium-ion secondary batteries.
[0004] Previous technical literature
[0005] Patent Literature
[0006] Patent Document 1: Japanese Patent Application Publication No. 2018-052755 Summary of the invention
[0007] Technical issues to be solved by the invention
[0008] Patent Document 1 discloses that the conductivity is 10 -5 S cm -1 However, in recent years, it is required to further improve the conductivity.
[0009] An object of the present invention is to provide a lithium-based solid electrolyte having excellent ion conductivity.
[0010] Furthermore, the present invention aims to provide a method for manufacturing a lithium-based solid electrolyte, a modified positive electrode active material, a modified negative electrode active material, an all-solid-state secondary battery, an electrode sheet for an all-solid-state secondary battery, a solid electrolyte sheet, and an electrode for an all-solid-state secondary battery.
[0011] Means for solving technical problems
[0012] The present inventors have conducted intensive studies to solve the above-mentioned problems and have completed the present invention having the following structure.
[0013] [1] A lithium-based solid electrolyte comprising amorphous lithium tetraborate, water and a lithium salt, wherein:
[0014] The water content is 45% by mass or less relative to the total mass of the lithium-based solid electrolyte.
[0015] [2] The lithium-based solid electrolyte according to [1], wherein
[0016] The above-mentioned lithium tetraborate has an OH structure.
[0017] [3] The lithium-based solid electrolyte according to [1] or [2], wherein:
[0018] The molar ratio of the lithium salt content to the lithium tetraborate content is 0.001 to 1.5, and the molar ratio of the water content to the lithium tetraborate content is 1 to 12.
[0019] [4] The lithium-based solid electrolyte according to any one of [1] to [3], wherein
[0020] The lithium salt is a compound represented by the formula (1) described later.
[0021] [5] The lithium-based solid electrolyte according to any one of [1] to [4], wherein
[0022] When a cross section of a molded body obtained by pressurizing the lithium-based solid electrolyte is observed with a scanning electron microscope, the region where the lithium salt exists exists in a mesh shape.
[0023] [6] A lithium-based solid electrolyte comprising lithium tetraborate and a lithium salt in an amorphous state, wherein:
[0024] When a cross section of a molded body obtained by pressurizing the lithium-based solid electrolyte is observed with a scanning electron microscope, the region where the lithium salt exists exists in a mesh shape.
[0025] [7] The lithium-based solid electrolyte according to [6], wherein
[0026] The above-mentioned lithium tetraborate has a hydroxyl group.
[0027] [8] The lithium-based solid electrolyte according to [6] or [7], wherein
[0028] The lithium salt is a compound represented by the formula (1) described later.
[0029] [9] A method for producing a lithium-based solid electrolyte, which is the method for producing a lithium-based solid electrolyte as described in any one of [1] to [8], comprising:
[0030] Step 1, subjecting a lithium-based oxide containing Li and B to mechanical grinding;
[0031] Step 2, mixing the product obtained in the above step 1 and water; and
[0032] Step 3, removing water from the dispersion obtained in the above step 2 to obtain a lithium-based solid electrolyte,
[0033] Satisfy any one of the requirements 1 to 3 described below.
[0034]
[10] The method for producing a lithium-based solid electrolyte according to [9], wherein:
[0035] In the step 3, the dispersion obtained in the step 2 is dried under the conditions of 20 Pa or less and 40° C. or less, thereby obtaining a lithium-based solid electrolyte.
[0036]
[11] The method for producing a lithium-based solid electrolyte according to [9] or
[10] , which satisfies the requirement 1 and, before the step 1, further includes a step 0: mechanically grinding a lithium-based oxide containing Li and B in the absence of the lithium salt.
[0037]
[12] A modified positive electrode active material, comprising a positive electrode active material and a coating layer disposed on the positive electrode active material, wherein:
[0038] The coating layer contains the lithium-based solid electrolyte described in any one of [1] to [8].
[0039]
[13] A modified negative electrode active material, comprising a negative electrode active material and a coating layer disposed on the negative electrode active material, wherein:
[0040] The coating layer contains the lithium-based solid electrolyte described in any one of [1] to [8].
[0041]
[14] An all-solid-state secondary battery comprising, in order, a positive electrode active material layer, a solid electrolyte layer, and a negative electrode active material layer, wherein:
[0042] At least one of the positive electrode active material layer, the solid electrolyte layer, and the negative electrode active material layer includes the lithium-based solid electrolyte described in any one of [1] to [8].
[0043]
[15] An electrode sheet for an all-solid-state secondary battery, comprising the lithium-based solid electrolyte described in any one of [1] to [8].
[0044]
[16] A solid electrolyte sheet comprising the lithium-based solid electrolyte described in any one of [1] to [8].
[0045]
[17] An electrode for an all-solid-state secondary battery, comprising:
[0046] An active material layer comprises an active material and the lithium-based solid electrolyte described in any one of [1] to [8]; and a current collector.
[0047] Effects of the Invention
[0048] According to the present invention, a lithium-based solid electrolyte having excellent ion conductivity can be provided.
[0049] Furthermore, according to the present invention, a method for manufacturing a lithium-based solid electrolyte, a modified positive electrode active material, a modified negative electrode active material, an all-solid-state secondary battery, an electrode sheet for an all-solid-state secondary battery, a solid electrolyte sheet, and an electrode for an all-solid-state secondary battery can also be provided. BRIEF DESCRIPTION OF THE DRAWINGS
[0050] Figure 1 This is a diagram showing an example of an X-ray diffraction pattern for explaining the requirement α.
[0051] Figure 2 This is a diagram showing an example of a reduced two-body distribution function G(r) obtained by total X-ray scattering measurement of a specific lithium tetraborate described later.
[0052] Figure 3 This is a diagram showing an example of total X-ray scattering distribution of specific lithium tetraborate described later.
[0053] Figure 4 Is based on Figure 3 A graph showing an example of the structure factor S(Q) of the total X-ray scattering distribution obtained in FIG.
[0054] Figure 5 This is an example of a Raman spectrum for explaining the element δ.
[0055] Figure 6 This is a conceptual diagram showing the state of water contained in the lithium-based solid electrolyte of the present invention.
[0056] Figure 7 The solid state of the first embodiment of the lithium-based solid electrolyte of the present invention is shown in FIG. 7 A diagram showing an example of a spectrum obtained during Li-NMR (Nuclear Magnetic Resonance) measurement.
[0057] Figure 8 It means that the solid state of lithium tetraborate crystals is carried out at 20℃ or 120℃ 7 A diagram showing an example of a spectrum obtained during Li-NMR measurement.
[0058] Fig. 9 The solid electrolyte of the first embodiment of the present invention is subjected to the reaction at 20°C. 7A diagram showing an example of a spectrum obtained during Li-NMR measurement.
[0059] Fig.10 Yes Fig. 9 The peak waveforms shown are separated.
[0060] Fig.11 The first embodiment of the lithium-based solid electrolyte of the present invention is shown. 1 An example of a spectrum obtained by H-NMR measurement.
[0061] Fig.12 This is a diagram showing an example of the Raman spectrum of the first embodiment of the lithium-based solid electrolyte of the present invention.
[0062] Fig.13 This is a diagram showing a Raman spectrum of a general lithium tetraborate crystal.
[0063] Fig.14 This is a diagram showing an example of a mapping image obtained by measuring the cross section of a molded body obtained by molding the second embodiment of the lithium-based solid electrolyte of the present invention by scanning electron microscopy-energy dispersive X-ray analysis (SEM-EDX).
[0064] Fig.15 This is a diagram showing an example of calculation results of the lithium-based solid electrolyte of the present invention based on the first principle molecular dynamics method.
[0065] Fig.16 It is a cross-sectional view schematically showing an all-solid-state lithium-ion secondary battery according to a preferred embodiment of the present invention.
[0066] Fig.17 An example of a graph obtained by thermogravimetric differential thermal analysis (TG-DTA) of the lithium-based solid electrolyte of the present invention is shown.
[0067] Fig.18 An example of a graph obtained by thermogravimetric mass spectrometry (TG-MS) of the lithium-based solid electrolyte of the present invention is shown.
[0068] Fig.19 The lithium-based solid electrolyte of the present invention 19 An example of a spectrum obtained by F-NMR measurement.
[0069] Fig. 20 ≠ 1 and 2 represent the reduced two-body distribution function G(r) obtained from the total X-ray scattering measurement of the crystal powder of Comparative Example 1.
[0070] Fig.21 The X-ray diffraction pattern of the crystal powder of Comparative Example 1 is shown.
[0071] Fig. 22The X-ray diffraction pattern of the lithium-based solid electrolyte of Example 4 is shown. DETAILED DESCRIPTION
[0072] Hereinafter, the present invention will be described in detail.
[0073] In addition, in this specification, the numerical range expressed using "to" means a range including the numerical values described before and after "to" as the lower limit and the upper limit.
[0074] As a characteristic point of the first embodiment of the lithium-based solid electrolyte of the present invention, the following point can be cited: lithium tetraborate in an amorphous state and a prescribed component (prescribed amount of water, lithium salt) are mixed and used. If lithium tetraborate in an amorphous state and a prescribed component are used together, a soft hydration layer is easily formed on the surface of lithium tetraborate, and a large amount of lithium derived from the lithium salt is contained in the hydration layer, so as a result, it is presumed that the ion conductivity becomes good.
[0075] As a characteristic point of the second embodiment of the lithium-based solid electrolyte of the present invention, the following point can be cited: in the molded body obtained by pressurizing the lithium-based solid electrolyte, the region where the lithium salt exists exists in a mesh shape. In the above-mentioned molded body, the region where the lithium salt exists (especially the region where the anion of the lithium salt exists) becomes a continuous phase, forming a mesh structure surrounding the lithium tetraborate particles, and functions as an excellent ion conduction path. Therefore, as a result, it is presumed that the ion conductivity becomes good.
[0076] Hereinafter, each embodiment of the lithium-based solid electrolyte of the present invention will be described in detail.
[0077] <<First embodiment>>
[0078] A first embodiment of the lithium-based solid electrolyte of the present invention (hereinafter also referred to as “the first lithium-based solid electrolyte”) includes lithium tetraborate in an amorphous state, and predetermined amounts of water and a lithium salt.
[0079] Hereinafter, each component will be described in detail.
[0080] (Amorphous lithium tetraborate)
[0081] Generally, lithium tetraborate contained in the first lithium-based solid electrolyte is composed of Li 2 B 4 O 7 The compounds represented by are mainly composed of Li, B and O, but in the present invention, the above standard values may be deviated. More specifically, as lithium tetraborate, preferably Li 2+x B 4+y O 7+zA compound represented by (-0.3<x<0.3, -0.3<y<0.3, -0.3<z<0.3).
[0082] Furthermore, lithium tetraborate contained in the first lithium-based solid electrolyte is in an amorphous state.
[0083] Amorphous lithium tetraborate (hereinafter also referred to as “specific lithium tetraborate”) refers to lithium tetraborate that satisfies the following requirement α.
[0084] Requirement α: In the X-ray diffraction pattern of lithium tetraborate in an amorphous state obtained from X-ray diffraction measurement using CuKα rays, there is no first peak with a peak top in the range of 21.6 to 22.0° and a full width at half maximum of 0.65° or less, no second peak with a peak top in the range of 25.4 to 25.8° and a full width at half maximum of 0.65° or less, no third peak with a peak top in the range of 33.4 to 33.8° and a full width at half maximum of 0.65° or less, and no fourth peak with a peak top in the range of 34.4 to 34.8° and a full width at half maximum of 0.65° or less, or
[0085] In the X-ray diffraction pattern, when there is at least one specific peak selected from the group consisting of a first peak, a second peak, a third peak and a fourth peak, at least one of the specific peaks has an intensity ratio calculated by the following intensity measurement method of 5.0 or less.
[0086] Intensity measurement method: The average intensity 1 in the range of +0.45° to +0.55° is calculated from the diffraction angle 2θ of the peak top of the specific peak, and the average intensity 2 in the range of -0.55° to -0.45° is calculated from the diffraction angle 2θ of the peak top of the specific peak, thereby calculating the arithmetic mean of the average intensity 1 and the average intensity 2, and the ratio of the peak intensity at the peak top of the specific peak to the arithmetic mean is set as the intensity ratio.
[0087] The specific lithium tetraborate may further satisfy the following requirement β.
[0088] Requirement β: In the reduced dimer distribution function G(r) obtained from the total X-ray scattering measurement of a specific lithium tetraborate, there is a peak located at r The first peak and the peak top in the range of r are The second peak in the range of , the peak G(r) of the first peak shows more than 1.0, and the peak G(r) of the second peak shows more than 0.8.
[0089] The specific lithium tetraborate preferably satisfies the above-mentioned requirement β. That is, the lithium tetraborate contained in the first lithium-based solid electrolyte preferably satisfies the above-mentioned requirement α and the above-mentioned requirement β.
[0090] The specific lithium tetraborate may further satisfy at least one of the following requirements γ and δ.
[0091] The specific lithium tetraborate preferably satisfies at least one of the above-mentioned requirements γ and δ. That is, the lithium tetraborate contained in the first lithium-based solid electrolyte more preferably satisfies the above-mentioned requirement α, satisfies the above-mentioned requirement β, and satisfies at least one of the above-mentioned requirements γ and δ.
[0092] Requirement γ: In the reduced two-body distribution function G(r) obtained from the total X-ray scattering measurement of a specific lithium tetraborate, when r is greater than and The absolute value of G(r) in the following range is less than 1.0.
[0093] Requirement δ: In the Raman spectrum of amorphous lithium tetraborate, the -1 With a peak and a full width at half maximum of 5 cm -1 The first peak above is at 770-790cm -1 With a peak and a full width at half maximum of 5 cm -1 The second peak above 1020-1040cm -1 With a peak and a full width at half maximum of 5 cm -1 None of the above third peaks exist, or
[0094] In the Raman spectrum, when at least one specific peak selected from the group consisting of a first peak, a second peak, and a third peak exists, a ratio to at least one intensity of the specific peak calculated by the following intensity measurement method is 5.0 or less.
[0095] Intensity measurement method: The 400-600 cm-1 Raman spectrum is -1 The minimum value M1 of the Raman intensity in the wave number region and the 1300-1500cm -1 The points of the minimum value M2 of the Raman intensity in the wave number region of 710-730 cm are connected to obtain a straight line, and in the region from the wave number indicating the above minimum value M1 to the wave number indicating the above minimum value M2, the peaks of the Raman intensity in the region of 710-730 cm are calculated. -1 、770~790cm -1 and 1020~1040cm -1 The average difference value between the Raman intensity of the above-mentioned straight line at each wavenumber in the area outside the area and the Raman intensity of the Raman spectrum is calculated, and the absolute value of the difference between the Raman intensity of the above-mentioned peak and the Raman intensity of the above-mentioned straight line at the wavenumber representing the peak top of the above-mentioned specific peak is calculated, and the ratio of the absolute value of the above-mentioned difference to the above-mentioned average difference value is set as the intensity ratio.
[0096] -Requirement α-
[0097] The requirement α will be described below.
[0098] First, in an X-ray diffraction pattern of a specific lithium tetraborate obtained from an X-ray diffraction measurement using CuKα rays, if none of the first peak having a peak top in the range of 21.6 to 22.0° and a full width at half maximum of 0.65° or less, the second peak having a peak top in the range of 25.4 to 25.8° and a full width at half maximum of 0.65° or less, the third peak having a peak top in the range of 33.4 to 33.8° and a full width at half maximum of 0.65° or less, and the fourth peak having a peak top in the range of 34.4 to 34.8° and a full width at half maximum of 0.65° or less do not exist, then requirement α is satisfied.
[0099] The full width at half maximum (FWHM) of a peak refers to the width (°) at a point where the intensity of the peak is 1 / 2.
[0100] Furthermore, in the X-ray diffraction pattern of a specific lithium tetraborate obtained from an X-ray diffraction measurement using CuKα rays, when there is at least one specific peak selected from the group consisting of a first peak, a second peak, a third peak, and a fourth peak, requirement α is satisfied even if the intensity ratio of at least one of the specific peaks calculated by the intensity measurement method described later is 5.0 or less.
[0101] Below, regarding the strength measurement method, Figure 1 Provide explanation.
[0102] Figure 1 This is a diagram showing an example of a specific peak appearing in a diffraction pattern of lithium tetraborate obtained from X-ray diffraction measurement using CuKα rays. Figure 1 In the diffraction pattern shown, the intensity of the peak top is shown to show a specific peak with an intensity of 1. In the intensity measurement method, as Figure 1 As shown, the average intensity 1 in the range of +0.45° to +0.55° is calculated from the diffraction angle 2θ of the peak top of the specific peak, and the average intensity 2 in the range of -0.55° to -0.45° is calculated from the diffraction angle 2θ of the peak top of the specific peak. Next, the arithmetic mean of the average intensity 1 and the average intensity 2 is calculated, and the ratio of the intensity 1 to the arithmetic mean is obtained as the intensity ratio.
[0103] When the above requirement α is satisfied, it means that the specific lithium tetraborate has no crystal structure or almost no crystal structure and is in an amorphous state.
[0104] That is, the 1st to 4th peaks recorded in the requirement α are peaks mainly derived from the crystal structure in the specific lithium tetraborate. In the absence of such peaks, there is no prescribed crystal structure in the specific lithium tetraborate and it is in an amorphous state, so it is inferred that, as described above, it is easy to form a hydrated layer with excellent ion conductivity. Moreover, even in the presence of at least one of the 1st to 4th peaks, the intensity ratio of any of the specific peaks is below the prescribed value, which indicates that there is almost no crystal structure in the specific lithium tetraborate, so it is inferred that, as described above, it is easy to form a hydrated layer with excellent ion conductivity. In addition, in the specific lithium tetraborate, peaks caused by other factors that are different from the peaks of the prescribed regular structure such as the crystal structure of lithium tetraborate are sometimes generated. As other factors, for example, peaks of regular structures derived from impurities can be cited, and such peaks sometimes overlap with the above-mentioned 1st to 4th peaks. In the case of achieving an amorphous state that can be presumed to be capable of forming a hydration layer with excellent ion conductivity, the 1st to 4th peaks will decrease in most cases. Assuming that, as described above, even if a peak caused by other factors coincidentally overlaps with any of the 1st to 4th peaks to form a large peak, there is a case where a specific peak has an intensity ratio below a specified value. It can be said that this indicates that the specific lithium tetraborate is in an amorphous state that can be presumed to be capable of forming a hydration layer with excellent ion conductivity.
[0105] The above X-ray diffraction measurement was performed using CuKα rays and under the measurement conditions of 0.01° / step, 3° / minute.
[0106] Regarding the above requirement α, in the X-ray diffraction spectrum of the specific lithium tetraborate obtained from the X-ray diffraction measurement using CuKα rays, when none of the first peak, the second peak, the third peak, and the fourth peak exists, or when a specific peak selected from the group consisting of the first peak, the second peak, the third peak, and the fourth peak exists, it is more preferred that at least one intensity ratio of the specific peaks is 3.0 or less. Among them, when none of the first peak, the second peak, the third peak, and the fourth peak exists, or when a specific peak selected from the group consisting of the first peak, the second peak, the third peak, and the fourth peak exists, it is further preferred that at least one intensity ratio of the specific peaks is 2.0 or less.
[0107] In addition, in the above-mentioned X-ray diffraction pattern of requirement α, when there are two or more peaks with peak tops in the range of 21.6 to 22.0° and a half-width of less than 0.65°, the peak with the largest diffraction X-ray intensity is selected as the first peak to perform the judgment of the above-mentioned requirement α.
[0108] Furthermore, in the above-mentioned X-ray diffraction pattern of requirement α, when there are two or more peaks with peak tops in the range of 25.4 to 25.8° and a full width at half maximum of less than 0.65°, the peak with the largest diffraction X-ray intensity is selected as the second peak to perform the judgment of the above-mentioned requirement α.
[0109] Furthermore, in the above-mentioned X-ray diffraction pattern of requirement α, when there are two or more peaks with peak tops in the range of 33.4 to 33.8° and a full width at half maximum of less than 0.65°, the peak with the largest diffraction X-ray intensity is selected as the third peak to perform the judgment of the above-mentioned requirement α.
[0110] Furthermore, in the above-mentioned X-ray diffraction pattern of requirement α, when there are two or more peaks with peak tops in the range of 34.4 to 34.8° and a full width at half maximum of less than 0.65°, the peak with the largest diffraction X-ray intensity is selected as the fourth peak to perform the judgment of the above-mentioned requirement α.
[0111] -Requirement β-
[0112] For element β, use Figure 2 to Figure 4 Provide explanation.
[0113] exist Figure 2 , an example of the reduced two-body distribution function G(r) obtained by total X-ray scattering measurement of specific lithium tetraborate is shown. Figure 2 The vertical axis is the reduced two-body distribution function obtained by Fourier transforming X-ray scattering, which represents the probability of the existence of an atom at a distance r.
[0114] SPring-8 BL04B2 (acceleration voltage 61.4keV, wavelength ) for total X-ray scattering measurements.
[0115] In addition, the scattering intensity I obtained by the experiment was transformed according to the following procedure to obtain the reduced two-body distribution function G(r).
[0116] First, the scattering intensity I obs It is represented by formula (1). And the structure factor S(Q) is obtained by dividing I coh It is obtained by dividing the product of the number of atoms N and the atomic scattering factor f.
[0117] I obs =I coh +I incoh +I 荧光 (1)
[0118] [Formula 1]
[0119]
[0120] The structure factor S(Q) is required in PDF (Pair Distribution Function) analysis. In the above equation (2), the required intensity is only the coherent scattering I coh . Incoherent scattering I incoh and Fluorescent X-ray I 荧光 can be used to subtract the theoretical formula using a blank measurement and the detector's discriminator from the scattered intensity I obs An example of the total scattering measurement results of a specific lithium tetraborate and the extracted structure factor S(Q) is shown in Figure 3 and Figure 4 middle.
[0121] Coherent scattering is expressed by Debye's scattering equation (3) (N: total number of atoms, f: atomic scattering factor, r ij : the interatomic distance between ij).
[0122] [Formula 2]
[0123]
[0124] If we focus on any atom and let the atomic density at a distance r be ρ(r), then the number of atoms existing in a sphere with a radius of r-r+d(r) is 4πr. 2 ρ(r)dr, so equation (3) is expressed by equation (4).
[0125] [Formula 3]
[0126]
[0127] If the average density of atoms is set to ρ 0 , and transforming (4), we can obtain formula (5).
[0128] [Formula 4]
[0129]
[0130] By using equation (5) and equation (2), equation (6) can be obtained.
[0131] [Formula 5]
[0132]
[0133] The two-body distribution function g(r) is expressed by equation (7).
[0134] [Formula 6]
[0135]
[0136] By using the above equations (6) and (7), equation (8) can be obtained.
[0137] [Formula 7]
[0138]
[0139] As mentioned above, the two-body distribution function can be obtained by Fourier transforming the structure factor S(Q). In order to easily observe the medium-range order / long-range order, the two-body distribution function is transformed into a function G(r)=4πr(g(r)-1) to reduce the two-body distribution function ( Figure 2 ). g(r) oscillating around 0 represents the density difference from the average density at each interatomic distance, and when there is a correlation at a specific interatomic distance, the average density becomes higher than 1. Therefore, the distance and coordination number of the element corresponding to the local to the intermediate distance are reflected. If the order disappears, ρ(r) approaches the average density, so g(r) gradually approaches 1. Therefore, in an amorphous structure, since the larger r becomes, the more the order disappears, g(r) becomes 1, that is, G(r) becomes 0.
[0140] In element β, if Figure 2 As shown, in the reduced two-body distribution function G(r) obtained from the total X-ray scattering measurement, there is a peak located at r The first peak P1 and the peak top are located at r within the range of The second peak P2 is within the range of , the peak G(r) of the first peak P1 shows more than 1.0 (preferably more than 1.2), and the peak G(r) of the second peak P2 shows more than 0.8 (preferably more than 1.0).
[0141] That is, in the reduction two-body distribution function G(r) obtained from the total X-ray scattering measurement of specific lithium tetraborate, a peak top (hereinafter also referred to as "the first peak top") was observed. G(r) showed a value exceeding 1.0, and the first peak top was located at The first peak and peak top (hereinafter also referred to as "second peak top") in the range of G(r) are greater than 0.8, and the second peak top is located at The second peak in the range.
[0142] In addition, Figure 2 The peak of the first peak P1 is located at The peak of the second peak P2 is located at
[0143] exist There is a peak at the position near B (boron)-O (oxygen) interatomic distance. There are peaks of interatomic distances attributed to B (boron)-B (boron) and O (oxygen)-O (oxygen) at nearby positions. That is, the observation of the above two peaks (the first peak and the second peak) means that a periodic structure corresponding to the above two interatomic distances exists in a specific lithium tetraborate. In addition, the interatomic distance of BO represents the distance between chemically bonded B and O, the interatomic distance of BB represents the distance between close B and B, and the interatomic distance of OO represents the distance between close O and O.
[0144] It is considered that the specific lithium tetraborate satisfying the above requirement γ has a short-range ordered structure related to the interatomic distances of BO, BB, and OO.
[0145] -Requirementsγ-
[0146] The above-mentioned requirement γ will be described below.
[0147] The reduced two-body distribution function G(r) obtained by total X-ray scattering measurement of specific lithium tetraborate in the requirement γ is the same as that in the above-mentioned requirement β.
[0148] And, in element γ, if Figure 2 As shown, when r is more than and In the following range, the absolute value of G(r) is less than 1.0 (corresponding to the dotted line).
[0149] As mentioned above, when r is greater than and When the absolute value of G(r) in the following range is less than 1.0, it means that there is almost no long-range ordered structure in the specific lithium tetraborate. Therefore, when the specific lithium tetraborate satisfies the requirement β, the specific lithium tetraborate itself shows elastic properties that are easily plastically deformed.
[0150] In addition, in the reduced two-body distribution function G(r) obtained from the total X-ray scattering measurement of specific lithium tetraborate, when r is In the following range, peaks other than the first peak and the second peak may exist.
[0151] -Requirement δ-
[0152] Hereinafter, the above-mentioned requirement δ will be described.
[0153] First, in the Raman spectrum of lithium tetraborate, the -1 The peak has a full width at half maximum of 5 cm -1 The first peak above is at 770-790cm -1 The peak has a full width at half maximum of 5 cm -1The second peak above 1020-1040cm -1 The peak has a full width at half maximum of 5 cm -1 When none of the above third peaks exists, the requirement δ is satisfied.
[0154] The full width at half maximum of a peak refers to the width (cm2) at the point where the peak height is half the height of the peak. -1 ).
[0155] Furthermore, in the Raman spectrum of a specific lithium tetraborate, when there is at least one specific peak selected from the group consisting of a first peak, a second peak, and a third peak, when the intensity ratio of at least one of the specific peaks calculated by the following intensity measurement method is 5.0 or less, the requirement T is also satisfied. Among all the specific peaks, it is preferred that the above intensity ratio is satisfied.
[0156] Below, regarding the strength measurement method, Figure 5 Provide explanation.
[0157] Figure 5 is a diagram showing an example of a Raman spectrum of a specific lithium tetraborate, wherein the vertical axis represents Raman intensity and the horizontal axis represents Raman shift. Figure 5 In order to facilitate understanding of the description, an example in which one specific peak exists is shown.
[0158] In the intensity measurement method, first, the 400-600 cm-1 band representing the specific lithium tetraborate in the Raman spectrum is -1 The point of the minimum Raman intensity M1 in the wave number region and the 1300-1500cm -1 The points of the minimum Raman intensity M2 in the wave number region are connected to obtain a straight line. Specifically, Figure 5 As shown, a point P1 indicating the minimum value M1 and a point P2 indicating the minimum value M2 are connected to obtain a straight line indicated by a dotted line.
[0159] Next, from the wave number representing the minimum value M1 ( Figure 5 W1 in the figure) to the wave number representing the minimum value M2 mentioned above ( Figure 5 In the area from 710 to 730 cm, the calculation -1 、770~790cm -1 and 1020~1040cm -1 The average difference between the Raman intensity of the straight line and the Raman intensity of the Raman spectrum at each wave number in the region other than the region (hereinafter referred to as the "specific region"). In addition, the average difference refers to the calculated average difference between the Raman intensity of the straight line and the Raman intensity of the Raman spectrum at each wave number from W1 to W2 in the specific region. -1The absolute value of the difference between the Raman intensity of the straight line at each wave number and the Raman intensity of the Raman spectrum is taken, and the absolute value of the difference is arithmetic averaged.
[0160] Next, the absolute value of the difference between the Raman intensity of the peak at the wave number representing the peak top of the specific peak and the Raman intensity of the straight line is calculated, and the ratio of the absolute value of the difference to the average difference value is calculated as the intensity ratio. More specifically, Figure 5 As shown, the absolute value (|S1-S2|) of the difference between the Raman intensity S1 of the peak at the wave number W3 representing the peak top and the Raman intensity S2 of the straight line at the wave number W3 is calculated, and it is investigated whether the absolute value of the obtained difference corresponds to less than 5.0 times the above-mentioned average difference value.
[0161] When the above requirement δ is satisfied, it means that the specific lithium tetraborate has no crystal structure or almost no crystal structure and is in an amorphous state.
[0162] That is, the 1st to 3rd peaks recorded in the requirement δ are peaks mainly derived from the crystal structure in the specific lithium tetraborate. In the absence of such peaks, there is no specified crystal structure in the specific lithium tetraborate and it is in an amorphous state, so it is inferred that, as described above, it is easy to form a hydrated layer with excellent ion conductivity. Moreover, even if there is at least one peak among the 1st to 3rd peaks, the intensity ratio of any of the specific peaks present is below the specified value, which indicates that there is almost no crystal structure in the specific lithium tetraborate, so it is inferred that, as described above, it is easy to form a hydrated layer with excellent ion conductivity. In addition, in the specific lithium tetraborate, peaks caused by other factors that are different from the peaks of the regular structure specified by the crystal structure of lithium tetraborate are sometimes generated. As other factors, for example, peaks of regular structures derived from impurities can be cited, and such peaks sometimes overlap with the 1st to 3rd peaks mentioned above. In the case of achieving an amorphous state that can be presumed to be capable of forming a hydration layer with excellent ion conductivity, the first to third peaks will decrease in most cases. Assuming that, as described above, even if a peak caused by other factors coincidentally overlaps with any of the first to third peaks to form a large peak, there is a case where a specific peak has an intensity ratio below a specified value. This can be said to indicate that the specific lithium tetraborate is in an amorphous state that can be presumed to be capable of forming a hydration layer with excellent ion conductivity.
[0163] In the Raman spectrum of the above-mentioned specific lithium tetraborate, when the first peak, the second peak and the third peak do not exist, or when a specific peak selected from the group including the first peak, the second peak and the third peak exists, it is more preferred that at least one intensity ratio of the specific peak is 3.0 or less. Among them, when the first peak, the second peak and the third peak do not exist, or when a specific peak selected from the group including the first peak, the second peak and the third peak exists, it is further preferred that at least one intensity ratio of the specific peak is 2.0 or less, and it is particularly preferred that the first peak, the second peak and the third peak do not exist.
[0164] In addition, as a method for measuring Raman spectroscopy, Raman imaging is implemented. Raman imaging refers to microscopic spectroscopy that combines Raman spectroscopy with microscopy. Specifically, it is a method that detects measurement light including Raman scattered light by scanning excitation light on a sample, and visualizes the distribution of components based on the intensity of the measurement light.
[0165] The measurement conditions of Raman imaging are as follows: 27°C and in the atmosphere, excitation light of 532nm, objective lens of 100 times, point scanning in mapping mode, 1μm step length, exposure time of 1 second per point, accumulation and integration times of 1 time, and measurement range of 70μm×50μm. However, the measurement range may become narrower depending on the film thickness of the sample.
[0166] Furthermore, the Raman spectrum data is subjected to principal component analysis (PCA) processing to remove noise. Specifically, in the principal component analysis processing, the spectrum is reorganized using components having an autocorrelation coefficient of 0.6 or more.
[0167] The bulk modulus of specific lithium tetraborate is not particularly limited, but is preferably 45 GPa or less, and more preferably 40 GPa or less, from the viewpoint of more excellent effects of the present invention. The lower limit is not particularly limited, but is preferably 5 GPa or more.
[0168] The measurement of the bulk modulus is performed by an ultrasonic attenuation method.
[0169] Specifically, first, a suspension obtained by suspending a specific lithium tetraborate in pure water was prepared. The content of the specific lithium tetraborate in the suspension was set to 1.2 mass % relative to the total mass of the suspension. Then, the ultrasonic attenuation spectrum of the above suspension was measured, and the bulk modulus of the specific lithium tetraborate was obtained by fitting based on the scattering attenuation theory formula. In addition, when performing the above fitting, the particle size distribution, density (2.3 g / ml) and Poisson's ratio (0.12) of the specific lithium tetraborate were used.
[0170] The bulk modulus was calculated by fitting the above-mentioned scattering attenuation theoretical formula using equations (7), (12) and (13) described in Kohjiro Kubo et al., Ultrasonics 62 (2015) 186-194.
[0171] The particle size distribution of the specific lithium tetraborate is determined by acquiring a particle image by flow particle image analysis to obtain a histogram (particle size distribution) of the particle size of the specific lithium tetraborate. The particle size is equivalent to an equivalent circle diameter.
[0172] The median particle size (D50) of the specific lithium tetraborate is not particularly limited, but is preferably 0.01 to 20 μm, more preferably 0.1 to 2.0 μm, from the viewpoint of achieving more excellent effects of the present invention.
[0173] The median particle size (D50) is measured by obtaining a particle image by flow particle image analysis, calculating the particle size distribution of the specific lithium tetraborate, and performing analysis based on the obtained distribution. In addition, the particle size corresponds to the equivalent circle diameter.
[0174] In order to further enhance the effect of the present invention, the specific lithium tetraborate preferably has an O (oxygen)-H (hydrogen) structure. The OH structure exists as a hydroxyl group or as a partial structure of a water molecule.
[0175] According to the measurement results of total X-ray scattering, it is considered that the specific lithium tetraborate in the amorphous state maintains BO represented by the following structural formula: 3 -BO 4 Connecting structure (diborate structure). Therefore, it is speculated that when a specific lithium tetraborate has a hydroxyl group, the hydroxyl group is bonded to any one of the boron atoms arranged around the following structural formula to form a partial structure of "B-OH". In addition, it is also speculated that water molecules exist in the hydration layer formed at the interface of the specific lithium tetraborate particles. Through any one or both OH structures, it is speculated that the conductivity of Li ions becomes good.
[0176] In addition, the fact that the specific lithium tetraborate has an OH structure can be confirmed by measuring the infrared absorption spectrum of the first lithium-based solid electrolyte as described later.
[0177] [Chemical formula 1]
[0178]
[0179] The content of the specific lithium tetraborate in the first lithium-based solid electrolyte is not particularly limited, but relative to the total mass of the first lithium-based solid electrolyte, it is, for example, 80% by mass or less, preferably 45% by mass or less, more preferably 40% by mass or less, further preferably 35% by mass or less, particularly preferably 30% by mass or less, and most preferably 25% by mass or less. In addition, the lower limit of the content of the specific lithium tetraborate is not particularly limited, but relative to the total mass of the lithium-based solid electrolyte, it is preferably 5% by mass or more, more preferably 10% by mass or more, further preferably 15% by mass or more, and particularly preferably 20% by mass or more.
[0180] The specific method for producing lithium tetraborate will be described in detail later, but it is preferably produced by a method accompanied by mechanical grinding. As the mechanical grinding treatment implemented on lithium tetraborate, the mechanical grinding treatment implemented in step 1A described later can be cited, and the details will be described in detail later.
[0181] By subjecting lithium tetraborate to mechanical polishing, lithium tetraborate can be amorphized, and as a result, it is presumed that a hydrated layer having excellent ion conductivity is easily formed.
[0182] (water)
[0183] The first lithium-based solid electrolyte contains water.
[0184] Furthermore, the content of water in the first lithium-based solid electrolyte is 45% by mass or less relative to the total mass of the lithium-based solid electrolyte. The first lithium-based solid electrolyte containing water at the above-mentioned content is solid and can move ions inside it. Furthermore, it is speculated that in the first lithium-based solid electrolyte containing water at the above-mentioned content, by forming a hydration layer in which Li ions and the like can move and function as an ion conduction path, excellent ion conductivity can be obtained.
[0185] Furthermore, if the first lithium-based solid electrolyte contains highly polar water, water interacts with the lithium salt, and Li and anions become easily dissociated, which is presumed to improve the conductivity of Li ions. In addition, part of the water may also dissociate and bond to the surrounding in the form of hydroxyl groups.
[0186] The water content in the first lithium-based solid electrolyte is preferably 40% by mass or less, more preferably 35% by mass or less, further preferably 30% by mass or less, and particularly preferably 25% by mass or less, relative to the total mass of the lithium-based solid electrolyte. In addition, the lower limit of the water content is not particularly limited, but is preferably 5% by mass or more, more preferably 10% by mass or more, further preferably 15% by mass or more, and particularly preferably 20% by mass or more, relative to the total mass of the lithium-based solid electrolyte.
[0187] Furthermore, from the viewpoint of achieving a more excellent effect of the present invention, the molar ratio of water to the specific lithium tetraborate in the first lithium-based solid electrolyte (molar amount of water / molar amount of specific lithium tetraborate) is preferably 1 to 12, and more preferably 1 to 10. Depending on the circumstances, the molar ratio of the above-mentioned water to the specific lithium tetraborate is more preferably 2 to 12. The molar ratio of water to the above-mentioned specific lithium tetraborate is further preferably 2 to 10, further preferably 2 to 8, particularly preferably 2 to 7, and most preferably 3 to 7.
[0188] The content and molar amount of water in the first lithium-based solid electrolyte can be obtained using a known method. For example, the content of various elements in the first lithium-based solid electrolyte can be determined by an elemental analysis method as described later, and the content and molar amount of water can be obtained based on the structure of the compound used.
[0189] The state of water contained in the first lithium-based solid electrolyte is described. Figure 6 As shown in the conceptual diagram, water contained in the first lithium-based solid electrolyte can be classified as follows depending on whether or not the water is desorbed (evaporated) from the first lithium-based solid electrolyte when the first lithium-based solid electrolyte is dried under predetermined conditions.
[0190] Water in the first state: evaporates when dried under the conditions of atmospheric pressure and 100° C. (the first condition).
[0191] Water in the second state: does not evaporate in the drying under the first condition, but evaporates when drying is performed under the conditions of 20 Pa and 40° C. (the second condition).
[0192] Water in the third state: does not evaporate in the drying under the first and second conditions, but evaporates when drying is performed under the conditions of 20 Pa and 100° C. (the third condition).
[0193] Water in the fourth state: does not evaporate during drying under the first to third conditions.
[0194] In addition, desorption from the first lithium-based solid electrolyte also includes a case where water is constrained by the surroundings and water is desorbed from the first lithium-based solid electrolyte when the constrained conditions become loose.
[0195] When the first lithium-based solid electrolyte is used in a battery, from the viewpoint of battery characteristics, it is preferred that the first lithium-based solid electrolyte does not contain the water in the first state and the water in the second state. In addition, when a molded body obtained by pressurizing the first lithium-based solid electrolyte is used in a battery, water in the second state may be contained.
[0196] Furthermore, when the first lithium-based solid electrolyte is used in a battery, the first lithium-based solid electrolyte preferably contains water in the third state from the viewpoint of achieving a good balance between ion conductivity and cycle characteristics.
[0197] (Lithium Salt)
[0198] The first lithium-based solid electrolyte contains a lithium salt.
[0199] The type of the lithium salt is not particularly limited, and examples thereof include the lithium salts exemplified in the step 1A described later, which will be described in detail later.
[0200] The content of the lithium salt in the first lithium-based solid electrolyte is not particularly limited.
[0201] The mass ratio of the content of lithium salt in the first lithium-based solid electrolyte to the content of the above-mentioned specific lithium tetraborate (the mass of the content of lithium salt / the mass of the content of specific lithium tetraborate) is not particularly limited. Among them, from the viewpoint of the better effect of the present invention, the molar ratio of lithium salt in the first lithium-based solid electrolyte to the specific lithium tetraborate (the molar amount of lithium salt / the molar amount of specific lithium tetraborate) is preferably 0.001 to 1.5, more preferably 0.001 to 1.2, further preferably 0.01 to 1.2, further preferably 0.1 to 1.2, particularly preferably 0.3 to 1.2, extremely preferably 0.5 to 1.2, and most preferably 0.5 to 1.0.
[0202] The first lithium-based solid electrolyte contains the elements Li, B, and O because it contains specific lithium tetraborate.
[0203] Furthermore, the first lithium-based solid electrolyte further preferably comprises one or more specific elements selected from the group consisting of elements of Group 4 of the periodic table, elements of Group 15 of the periodic table, elements of Group 16 of the periodic table, elements of Group 17 of the periodic table, Si, C, Sc, and Y, and more preferably comprises two or more specific elements. In addition, from the viewpoint of the better effect of the present invention, the first lithium-based solid electrolyte preferably comprises one or more (more preferably two or more) specific elements selected from the group consisting of F, Cl, Br, I, S, P, Si, Se, Te, C, Sb, As, Sc, Y, Zr, Ti, Hf, and N.
[0204] Examples of the periodic table Group 4 elements include Ti, Zr, Hr, and Rf.
[0205] Examples of the periodic table Group 15 elements include N, P, As, Sb, Bi, and Mc.
[0206] Examples of the periodic table Group 16 elements include S, Se, Te, Po, and Lv.
[0207] Examples of the periodic table Group 17 elements include F, Cl, Br, I, At, and Ts.
[0208] The number of specific elements contained in the first lithium-based solid electrolyte may be 3 or more. From the viewpoint of achieving a more excellent effect of the present invention, the number of specific elements contained in the lithium-based solid electrolyte is preferably 2 or more, more preferably 2 to 5, and even more preferably 2 to 4.
[0209] The first lithium-based solid electrolyte preferably contains two or more specific elements selected from the group consisting of F, S, N, P, C, Cl and I, more preferably contains two or more specific elements selected from the group consisting of F, S, C and N, and further preferably contains three specific elements of F, S and N.
[0210] The above-mentioned specific elements are, for example, elements derived from lithium salts in many cases.
[0211] In the first lithium-based solid electrolyte, when the molar amount of Li is expressed by setting the molar amount of B in the lithium-based solid electrolyte to 4.00, the molar amount of Li is preferably 1.58 to 3.49. That is, when the molar content of B is 4.00, the relative value of the molar content of Li is preferably 1.58 to 3.49.
[0212] Among them, from the viewpoint of more excellent effects of the present invention, when the molar amount of B in the lithium-based solid electrolyte is set to 4.00 to represent the molar amount of Li, the molar amount of Li is more preferably 1.58 to 3.00, further preferably 1.90 to 3.00, further preferably 2.00 to 3.00, particularly preferably 2.30 to 3.00, and most preferably 2.50 to 3.00.
[0213] In the first lithium-based solid electrolyte, when the molar amount of B in the lithium-based solid electrolyte is set to 4.00 to represent the molar amount of O, the molar amount of O is preferably 6.23 to 25.00. That is, when the molar content of B is set to 4.00, the relative value of the molar content of O is preferably 6.23 to 25.00.
[0214] Among them, from the viewpoint of more excellent effects of the present invention, when the molar amount of O is represented by 4.00 as the molar amount of B in the lithium-based solid electrolyte, the molar amount of O is more preferably 8.00 to 23.00, further preferably 10.00 to 23.00, and particularly preferably 10.00 to 17.00.
[0215] In the first lithium-based solid electrolyte, when the molar amount of B in the lithium-based solid electrolyte is set to 4.00 to represent the molar amount of the specific element, the molar amount of each specific element is preferably 0.001 to 10.00. That is, when the molar content of B is set to 4.00, the relative value of the molar content of each specific element is preferably 0.001 to 10.00.
[0216] Among them, from the viewpoint of better effect of the present invention, when the molar amount of B in the lithium-based solid electrolyte is set to 4.00 to represent the molar amount of the specific element, the molar amount of each specific element is more preferably 0.001 to 6.0, further preferably 0.01 to 5.0, further preferably 0.01 to 4.0, especially preferably 0.01 to 3.0, and most preferably 0.01 to 2.0.
[0217] As described above, in the first lithium-based solid electrolyte, it is preferred that two or more specific elements are included. Thus, for example, when the first lithium-based solid electrolyte includes two specific elements, namely, a specific element A and an element of a different type from the specific element A, namely, a specific element B, when the molar amount of B in the lithium-based solid electrolyte is set to 4.00, the molar amount of the specific element A and the molar amount of the specific element B are 0.001 to 10.00, respectively. And, for example, when the first lithium-based solid electrolyte includes three specific elements, namely, a specific element A, an element of a different type from the specific element A, namely, a specific element B, and an element of a different type from the specific elements A and B, namely, a specific element C, when the molar amount of B in the lithium-based solid electrolyte is set to 4.00, the molar amount of the specific element A, the molar amount of the specific element B, and the molar amount of the specific element C are 0.001 to 10.00, respectively.
[0218] In addition, the molar ratio and content of each component in the first lithium-based solid electrolyte can be obtained using a known method. For example, the content of each element in the first lithium-based solid electrolyte can be determined, and the molar ratio and content of each component can be determined based on the structure of the compound used. As a method of elemental analysis, for example, Na and B are analyzed by ICP-OES (Inductively coupled plasma optical emission spectrometry), N, etc. are analyzed by inert gas fusion method, and F and S are analyzed by combustion ion chromatography. Regarding O, the analysis mass of elements other than O can be added and calculated as a difference from the total amount of powder. In addition, the method for calculating the content of each element is not limited to the above. Considering the structure of the compound used, the content of other elements can be estimated based on the analysis results of the content of one element.
[0219] (Characteristics of lithium-based solid electrolytes)
[0220] TG-MS measurement
[0221] From the viewpoint of achieving a more excellent effect of the present invention, when thermogravimetry mass spectrometry (TG-MS) is performed on the molded body obtained by pressurizing the first lithium-based solid electrolyte, it is preferred to detect the component with a molecular weight of 18 in a temperature range exceeding 100°C, and it is more preferred to detect the component with a molecular weight of 18 in a temperature range exceeding 120°C.
[0222] The results of TG-MS on the molded body of the lithium-based solid electrolyte are as follows: when a component with a molecular weight of 18 is detected in a temperature range exceeding 100°C, water (especially the water in the third and fourth states described above) is present in the lithium-based solid electrolyte. It is believed that the water present in the lithium-based solid electrolyte (especially the water in the third and fourth states described above) contributes to ion conductivity.
[0223] The TG-MS measurement method of the molded body using the lithium-based solid electrolyte will be described in detail in the examples described later.
[0224] · 7 Li-NMR measurements
[0225] From the viewpoint of achieving a more excellent effect of the present invention, the solidification of the first lithium-based solid electrolyte was performed at 120°C. 7 The full width at half maximum of the peak whose chemical shift appears in the range of -100 to +100 ppm in the spectrum obtained by Li-NMR measurement is relative to the solid-state reaction of the first lithium-based solid electrolyte at 20°C. 7 The ratio of the full width at half maximum of the peak whose chemical shift in the spectrum obtained during Li-NMR measurement appears in the range of -100 to +100 ppm is preferably 50% or less, more preferably 40% or less, and further preferably 35% or less. The lower limit is not particularly limited, but is 10% or more in most cases.
[0226] The full width at half maximum (FWHM) of a peak refers to the width (ppm) at a point (H / 2) that is 1 / 2 of the height (H) of the peak.
[0227] Below, use Figure 7 The above characteristics are described.
[0228] exist Figure 7 In the embodiment, the solid state of the first lithium-based solid electrolyte is shown at 20°C or 120°C. 7 An example of a spectrum obtained during Li-NMR measurement.
[0229] exist Figure 7 The solid line spectrum shown on the lower side is the solid state spectrum at 20°C. 7 The spectrum obtained during Li-NMR measurement is Figure 7 The dotted spectrum shown on the upper side is a spectrum obtained by solid-state heating at 120°C. 7 Spectra obtained during Li-NMR measurement.
[0230] Generally speaking, in solid 7 In Li-NMR measurement, Li + In case of high mobility, the peak obtained is sharper. Figure 7 In the manner shown, when comparing the spectrum at 20°C with the spectrum at 120°C, the spectrum at 120°C becomes sharper. Figure 7 In the lithium-based solid electrolyte shown, Li + The mobility of lithium-based solid electrolytes increases. It is believed that this lithium-based solid electrolyte is prone to plastic deformation due to its amorphous structure, and Li + The jumping property is excellent, so the effect of the present invention is more excellent.
[0231] In addition, for example, regarding lithium tetraborate crystals, solid-state 7 During Li-NMR measurement, Figure 8 The spectrum measured at 20°C is shown on the lower side of Figure 8 The spectra measured at 120° C. and indicated by the dotted line shown on the upper side of tend to have substantially the same shape.
[0232] The above solid 7 Li-NMR measurement conditions are as follows.
[0233] Specifically, a 4 mm HX CP-MAS probe was used and measurement was performed by a single pulse method with a 90° pulse width of 3.2 μs, an observation frequency of 155.546 MHz, an observation width of 1397.6 ppm, a repetition time of 15 seconds, a cumulative integration of 1 time, and a MAS rotation speed of 0 Hz.
[0234] Furthermore, from the viewpoint of achieving a more excellent effect of the present invention, it is preferred that the first lithium-based solid electrolyte be solidified at 20°C. 7When the first peak in the spectrum obtained during Li-NMR measurement that appears in the range of -100 to +100 ppm is subjected to waveform separation, there is a second peak with a chemical shift in the range of -3 to 3 ppm and a half-peak width of 5 ppm or less, and the ratio of the area intensity of the second peak to the area intensity of the first peak is 0.5% or more. The ratio of the above-mentioned area intensity is more preferably 2% or more, and further preferably 15% or more. The upper limit of the ratio of the above-mentioned area intensity is not particularly limited, but in most cases it is 50% or less.
[0235] Below, use Fig. 9 and Fig.10 The above characteristics are described.
[0236] exist Fig. 9 The solid state of the first lithium-based solid electrolyte is shown at 20°C. 7 An example of a spectrum obtained during Li-NMR measurement. Fig. 9 As shown, in the first lithium-based solid electrolyte, a peak (corresponding to the first peak) is observed in the range of -100 to +100 ppm, and in the first peak, a small peak surrounded by a dotted line is observed near the chemical shift of 0 ppm. + When the mobility is high, a sharp peak can be observed, thus producing its influence.
[0237] Then, in Fig.10 , a diagram showing the separation of the first peak waveform is shown. Fig.10 As shown, the first peak is separated into a small peak (corresponding to the second peak) represented by a solid line and a large peak represented by a dotted line. The second peak is a peak with a chemical shift in the range of -3 to 3 ppm and a full width at half maximum of less than 5 ppm.
[0238] In the first lithium-based solid electrolyte, Fig.10 The solid line represents the area intensity of the second peak relative to that of Fig. 9 The ratio of the area intensity of the first peak (the peak before the waveform separation) {(area intensity of the second peak / area intensity of the first peak)×100} represented is within the above range.
[0239] As a method of waveform separation, a method using known software can be mentioned. As software, for example, Igor Pro, a graphics processing software of WaveMetrics, Inc. can be mentioned.
[0240] · 1 H-NMR measurements
[0241] From the viewpoint of achieving a more excellent effect of the present invention, it is preferred that the first lithium-based solid electrolyte 1The chemical shift in the spectrum obtained by H-NMR measurement is within the range of -200 to +200 ppm, and both a sharp peak and a broad peak appear. In addition, a "sharp peak" refers to a peak with a half-maximum width of 50 ppm or less, and a "broad peak" refers to a peak with a half-maximum width of 50 ppm or more.
[0242] Below, use Fig.11 The above characteristics are described.
[0243] exist Fig.11 In the figure, the first lithium-based solid electrolyte is subjected to 1 An example of a spectrum obtained by H-NMR measurement.
[0244] Usually, in 1 In H-NMR measurement, when the mobility of hydrogen atoms is high, a sharper peak can be obtained. Fig.11 In the spectrum shown, a peak value composed of a sharp peak and a broad peak appears. Fig.11 In the lithium-based solid electrolyte shown, there are hydrogen atoms with high relative mobility corresponding to the sharp peak and hydrogen atoms with low mobility corresponding to the broad peak. It is speculated as follows: the hydrogen atoms with high relative mobility contained in this lithium-based solid electrolyte are contained in the above-mentioned hydration layer and are related to the conduction of lithium ions.
[0245] In addition, for example, with respect to lithium tetraborate crystals, at 20°C 1 In H-NMR measurement, a sharp peak does not appear in the chemical shift range of -200 to +200 ppm, but only a broad peak tends to appear.
[0246] Above 1 H-NMR measurement conditions are as follows.
[0247] Specifically, a 4 mm HX CP-MAS probe was used, and the measurement was performed by a composite pulse method at a measurement temperature of 20° C. with a 90° pulse width of 2.5 μs, an observation frequency of 400.23092 MHz, an observation width of 694.043 ppm, a repetition time of 20 seconds, a cumulative and integrated number of times: 16 times, and a MAS rotation speed of 0 Hz.
[0248] · 19 F-NMR measurements
[0249] From the viewpoint of achieving a more excellent effect of the present invention, when the lithium salt contains fluorine atoms, it is preferred to pass the first lithium-based solid electrolyte. 19 The chemical shift in the spectrum obtained by F-NMR measurement is within the range of -200 to +300 ppm, and a sharp peak with a full width at half maximum of 20 ppm or less appears.
[0250] The lithium salt or the anion of the lithium salt is considered to contribute to the ion conductivity, but it is suggested that in the lithium-based solid electrolyte having a sharp peak in the above range, the mobility of the lithium salt or the anion of the lithium salt is relatively high.
[0251] Above 19 The F-NMR measurement conditions are as follows.
[0252] Specifically, a 4 mm HXCP-MAS probe was used and measurement was performed by a single pulse method with a 90° pulse width of 3.5 μs, an observation frequency of 376.59246 MHz, an observation width of 603.497 ppm, a repetition time of 10 seconds, a cumulative integration of 1 time, and a MAS rotation speed of 0 Hz.
[0253] TG-DTA measurement
[0254] From the viewpoint of more excellent effects of the present invention, the mass reduction rate when the first lithium-based solid electrolyte is heated to 800° C. is preferably 20 to 40 mass %, and from the viewpoint of more excellent effects of the present invention, the mass reduction rate is more preferably 25 to 35 mass %.
[0255] The mass reduction of the first lithium-based solid electrolyte generated during the above heating is believed to be caused by the removal of a portion of the water contained in the lithium-based solid electrolyte. As shown above, the situation showing a predetermined amount of mass reduction rate indicates that a predetermined amount of water is contained in the lithium-based solid electrolyte, and it is believed that the conductivity of lithium ions is improved by the presence of this predetermined amount of water.
[0256] When the heat treatment is performed, heating is performed at a temperature increase rate of 20° C. / second in a range from 25° C. to 800° C. In addition, a known thermogravimetric differential thermal analysis (TG-DTA) apparatus can be used for measurement.
[0257] The mass reduction rate is calculated by {(mass at 25° C.−mass at 800° C.) / mass at 25° C.}×100.
[0258] In order to perform the above-mentioned heat treatment, the first lithium-based solid electrolyte was vacuum-dried at 40° C. for 2 hours and then measured in the atmosphere.
[0259] Ionic conductivity
[0260] From the viewpoint of achieving a more excellent effect of the present invention, the ion conductivity of the molded body obtained by pressurizing the first lithium-based solid electrolyte at -10°C is preferably 1×10 -5 S / cm or more, more preferably 1×10 -4 S / cm or more. The upper limit is not particularly limited, but in many cases it is 1×10 -3S / cm or less.
[0261] When the molded body of the lithium-based solid electrolyte shows the ion conductivity in the above range under the temperature condition of -10°C, it is suggested that in addition to the water in the first and second states, there are substances that contribute to ion conductivity in the lithium-based solid electrolyte, thereby forming a good ion conduction path. It is believed that in this lithium-based solid electrolyte, even at room temperature (27°C), it has excellent ion conductivity.
[0262] The method for measuring the ion conductivity at -10°C of a molded body obtained by pressurizing a lithium-based solid electrolyte will be described in detail in the examples described later.
[0263] SEM-EDX analysis
[0264] From the viewpoint of achieving more excellent effects of the present invention, the first lithium-based solid electrolyte preferably has a region where the lithium salt exists in a mesh shape when a cross section of a molded body obtained by pressing the first lithium-based solid electrolyte is observed with a scanning electron microscope (SEM).
[0265] The above-mentioned characteristics and their measurement methods will be described in detail in the second embodiment to be described later.
[0266] Infrared absorption spectrum
[0267] From the viewpoint of achieving a more excellent effect of the present invention, in the infrared absorption spectrum of the first lithium-based solid electrolyte, the -1 The maximum absorption intensity in the wave number region is relatively large compared to that in the region of 800 to 1600 cm -1 The ratio of the maximum absorption intensity in the wave number region is preferably 1 / 5 or more. Among them, from the viewpoint of the better effect of the present invention, the above ratio is preferably 3 / 10 or more, more preferably 2 / 5 or more. The upper limit is not particularly limited, but is preferably 1 or less.
[0268] In the infrared absorption spectrum, the range of 3000 to 3500 cm -1 The OH stretching vibration mode is observed in the wave number region of 800-1600 cm -1The BO stretching vibration mode is observed in the wave number region. The absorption intensity derived from the above-mentioned OH stretching vibration mode is derived from the hydroxyl group or water contained in the lithium-based solid electrolyte. In particular, in the first lithium-based solid electrolyte, when the absorption intensity derived from the above-mentioned OH stretching vibration mode is observed to be strong, it is believed that the specific lithium tetraborate contained in the first lithium-based solid electrolyte usually has a large number of OH structures. In this lithium-based solid electrolyte, lithium ions become easy to move, and as a result, it is believed that the ion conductivity is improved.
[0269] In addition, at 800-1600cm -1 In the wave number region, vibration modes originating from lithium salts can also be observed.
[0270] The above-mentioned infrared absorption spectrum measurement conditions are as follows.
[0271] Specifically, objective lens: 32x Cassegrain (NA 0.65), detector: MCT-A, measurement range: 650-4000 cm -1 , Resolution: 4cm -1 , Sample cell: Use diamond cell for measurement.
[0272] In addition, regarding the infrared absorption spectrum obtained, in order to remove water and CO from the atmosphere 2 The signal is corrected and an offset correction is applied to the background to make the absorption intensity zero.
[0273] Furthermore, when measuring the infrared absorption spectrum of the first lithium-based solid electrolyte, the spectrum was vacuum-dried at 40° C. for 2 hours and then measured in the atmosphere.
[0274] Raman spectroscopy
[0275] Furthermore, from the viewpoint of achieving a more excellent effect of the present invention, the first lithium-based solid electrolyte has a Raman spectrum of 600 to 850 cm -1 The coefficient of determination obtained by performing linear regression analysis using the least squares method in the wavenumber region is preferably 0.9400 or more.
[0276] In addition, from the viewpoint of achieving more excellent effects of the present invention, the coefficient of determination is more preferably 0.9600 or more. The upper limit is not particularly limited, but 1.0000 is exemplified.
[0277] Below, use Fig.12 The above characteristics are described.
[0278] exist Fig.12 , an example of the Raman spectrum of the first lithium-based solid electrolyte is shown. The vertical axis is the Raman intensity and the horizontal axis is the Raman shift in the 600-850 cm Raman spectrum. -1The coefficient of determination (R 2 ). That is, in Fig.12 The Raman spectrum of 600-850 cm -1 In the wave number region, the regression line is obtained by the least square method ( Fig.12 The bold line in the figure is used to calculate the coefficient of determination R of the regression line. 2 In addition, the coefficient of determination takes a value between 0 (no linear correlation) and 1 (complete linear correlation of the measured values) depending on the linear correlation of the measured values.
[0279] In the first lithium-based solid electrolyte, Figure 2 As shown, at 600-850cm -1 Almost no peak was observed in the wavenumber region, and as a result, a high determination coefficient was shown.
[0280] In addition, the above determination coefficient R 2 It is equivalent to the square of the correlation coefficient (Pearson product-moment correlation coefficient). More specifically, in this specification, the coefficient of determination R 2 The calculation is done by the following formula. 1 and 1 represents the wave number in the Raman spectrum and the Raman intensity corresponding to its wave number, x 2 represents the (additive) mean of the wave numbers, y 2 represents the (additive) average of the Raman intensities.
[0281] [Formula 8]
[0282]
[0283] On the other hand, Fig.13 The Raman spectrum of a typical lithium tetraborate crystal is shown in FIG. Fig.13 As shown, in the case of a conventional lithium tetraborate crystal, the wavelengths of 716 to 726 cm-1 are derived from its structure. -1 and 771~785cm -1 A peak is observed in the wavenumber region.
[0284] In the presence of such a peak, the -1 In the wave number region, when the coefficient of determination was calculated by linear regression analysis using the least squares method, the coefficient of determination was less than 0.9400.
[0285] That is, the case where the determination coefficient is 0.9400 or more indicates that the first lithium-based solid electrolyte contains almost no crystal structure such as that contained in the usual lithium tetraborate crystal. Therefore, as a result, it is considered that the first lithium-based solid electrolyte has Li +Excellent jumping properties.
[0286] Karl Fischer measurement
[0287] From the viewpoint of a more excellent effect of the present invention, after drying the molded body obtained by pressurizing the first lithium-based solid electrolyte by a prescribed method, when measuring the water content evaporated from the obtained molded body based on the Karl Fischer method, it is preferred that the water content B evaporated from the first lithium-based solid electrolyte during heating from room temperature to 200°C is greater than the water content A evaporated from the first lithium-based solid electrolyte during heating from room temperature (27°C) to 100°C.
[0288] The fact that the water content B is greater than the water content A indicates that water that is more strongly bound to the surroundings than the water in the first state exists in the first lithium-based solid electrolyte, and the presence of such a predetermined amount of water is considered to contribute to the conductivity of lithium ions.
[0289] In addition, a method for drying the molded body obtained by pressurizing the first lithium-based solid electrolyte and a method for measuring the water content by the Karl Fischer method are described in the examples described later.
[0290] ·Requirement T
[0291] From the viewpoint of achieving more excellent effects of the present invention, the first lithium-based solid electrolyte preferably satisfies the following requirement T.
[0292] Requirement T: In the Raman spectrum of lithium-based solid electrolytes, the -1 With a peak and a full width at half maximum of 5 cm -1 The first peak above is at 770-790cm -1 With a peak and a full width at half maximum of 5 cm -1 The second peak above 1020-1040cm -1 With a peak and a full width at half maximum of 5 cm -1 None of the above third peaks exist, or,
[0293] In the Raman spectrum, when at least one specific peak selected from the group consisting of a first peak, a second peak, and a third peak exists, a ratio to at least one intensity of the specific peak calculated by the following intensity measurement method is 5.0 or less.
[0294] Intensity measurement method: The 400-600 cm-1 Raman spectrum is -1 The minimum value M1 of the Raman intensity in the wave number region and the 1300-1500cm -1The points of the minimum value M2 of the Raman intensity in the wave number region of 710-730 cm are connected to obtain a straight line, and in the region from the wave number indicating the above minimum value M1 to the wave number indicating the above minimum value M2, the peaks of the Raman intensity in the region of 710-730 cm are calculated. -1 、770~790cm -1 and 1020~1040cm -1 The average difference value between the Raman intensity of the above-mentioned straight line at each wavenumber in the area outside the area and the Raman intensity of the Raman spectrum is calculated, and the absolute value of the difference between the Raman intensity of the above-mentioned peak and the Raman intensity of the above-mentioned straight line at the wavenumber representing the peak top of the above-mentioned specific peak is calculated, and the ratio of the absolute value of the above-mentioned difference to the above-mentioned average difference value is set as the intensity ratio.
[0295] The requirement T is a requirement evaluated by the same procedure except that the first lithium-based solid electrolyte is used as the object to be measured for the requirement δ described above, and the evaluation method is as described above.
[0296] In the Raman spectrum of the above-mentioned lithium-based solid electrolyte, when the first peak, the second peak, and the third peak do not exist, or when a specific peak selected from the group including the first peak, the second peak, and the third peak exists, it is more preferred that at least one intensity ratio of the specific peak is 3.0 or less. Among them, when the first peak, the second peak, and the third peak do not exist, or when a specific peak selected from the group including the first peak, the second peak, and the third peak exists, it is further preferred that at least one intensity ratio of the specific peak is 2.0 or less, and it is particularly preferred that the first peak, the second peak, and the third peak do not exist.
[0297] ·Requirement X
[0298] From the viewpoint of achieving more excellent effects of the present invention, the first lithium-based solid electrolyte preferably satisfies the following requirement X.
[0299] Requirement X: In the reduced two-body distribution function G(r) obtained from the total X-ray scattering measurement of lithium-based solid electrolytes, there is a peak located at r. The first peak and the peak top in the range of r are The second peak in the range of , the peak G(r) of the first peak shows more than 1.0 (preferably more than 1.2), and the peak G(r) of the second peak shows more than 0.8 (preferably more than 1.0).
[0300] Requirement X corresponds to the above-mentioned requirement β, and its technical meaning is as described above, that a periodic structure corresponding to the interatomic distance of B (boron)-O (oxygen), the interatomic distance of B (boron)-B (boron) and the interatomic distance of O (oxygen)-O (oxygen) exists in the lithium-based solid electrolyte.
[0301] In requirement X, as described above, the peak top G(r) of the first peak is preferably 1.2 or more, and the peak top G(r) of the second peak is preferably more than 1.0.
[0302] The measurement method of requirement X is the same as that of requirement β described above.
[0303] ·Requirement Y
[0304] From the viewpoint of achieving more excellent effects of the present invention, the first lithium-based solid electrolyte preferably satisfies the following requirement Y.
[0305] Requirement Y: In the X-ray diffraction pattern of the lithium-based solid electrolyte obtained from X-ray diffraction measurement using CuKα rays, there is no first peak with a peak top in the range of 21.6 to 22.0° and a full width at half maximum of 0.65° or less, no second peak with a peak top in the range of 25.4 to 25.8° and a full width at half maximum of 0.65° or less, no third peak with a peak top in the range of 33.4 to 33.8° and a full width at half maximum of 0.65° or less, and no fourth peak with a peak top in the range of 34.4 to 34.8° and a full width at half maximum of 0.65° or less, or
[0306] In the X-ray diffraction pattern, when there is at least one specific peak selected from the group consisting of a first peak, a second peak, a third peak and a fourth peak, at least one of the specific peaks has an intensity ratio calculated by the following intensity measurement method of 5.0 or less.
[0307] Intensity measurement method: The average intensity 1 in the range of +0.45° to +0.55° is calculated from the diffraction angle 2θ of the peak top of the specific peak, and the average intensity 2 in the range of -0.55° to -0.45° is calculated from the diffraction angle 2θ of the peak top of the specific peak, thereby calculating the arithmetic mean of the average intensity 1 and the average intensity 2, and the ratio of the peak intensity at the peak top of the specific peak to the arithmetic mean is set as the intensity ratio.
[0308] Requirement Y is a requirement evaluated by the same procedure except that the first lithium-based solid electrolyte is used as the measurement object of the above-mentioned requirement α, and the evaluation method is as described above.
[0309] In the X-ray diffraction spectrum obtained from the X-ray diffraction measurement using CuKα rays of the first embodiment of the above-mentioned lithium-based solid electrolyte, when the first peak, the second peak, the third peak, and the fourth peak do not exist, or when a specific peak selected from the group including the first peak, the second peak, the third peak, and the fourth peak exists, it is more preferred that at least one intensity ratio of the specific peak is 3.0 or less. Among them, when the first peak, the second peak, the third peak, and the fourth peak do not exist, or when a specific peak selected from the group including the first peak, the second peak, the third peak, and the fourth peak exists, it is further preferred that at least one intensity ratio of the specific peak is 2.0 or less.
[0310] <<Second embodiment>>
[0311] A second embodiment of the lithium-based solid electrolyte of the present invention (hereinafter also referred to as “a second lithium-based solid electrolyte”) includes lithium tetraborate and a lithium salt in an amorphous state.
[0312] Furthermore, in the second lithium-based solid electrolyte, when a cross section of a molded body obtained by pressurizing the second lithium-based solid electrolyte is observed with a scanning electron microscope (SEM), a region where the lithium salt exists exists in a mesh shape.
[0313] As a method for observing the cross section of the molded body of the second lithium-based solid electrolyte by SEM, for example, a method of detecting the above-mentioned specific elements and other elements derived from the lithium salt by energy dispersive X-ray spectrometry (EDX) to obtain a mapping image representing the composition distribution on the cross section can be cited. The detection element can be appropriately selected according to the type of lithium salt, but is preferably sulfur, nitrogen or a halogen atom, and more preferably sulfur.
[0314] The method for forming the cross section of the molded body of the second lithium-based solid electrolyte is not particularly limited, but it is preferable to form the cross section using a cross section polisher (CCP) device.
[0315] Below, use Fig.14 The above characteristics are described.
[0316] exist Fig.14 , an example of a mapping image showing a cross section of a molded body of a second lithium-based solid electrolyte obtained by SEM-EDX analysis is shown. Fig.14In the mapping image shown, the region where the lithium salt exists is represented by the bright part, and the region where the lithium salt does not exist (specifically the region where lithium tetraborate exists) is represented by the dark part, and the bright part forms a mesh-like continuous phase surrounding the dark part. In the molded body of the lithium-based solid electrolyte, a mesh-like structure is formed by the lithium salt that contributes to ion conduction, thereby forming a good ion conduction path connecting the electrodes, so it is believed that the effect of the present invention can be obtained.
[0317] The method of analyzing the cross section of the molded body of the lithium-based solid electrolyte by SEM-EDX and the method of producing the cross section of the molded body of the lithium-based solid electrolyte will be described in detail in the examples described later.
[0318] The second lithium-based solid electrolyte includes lithium tetraborate (specific lithium tetraborate) in an amorphous state.
[0319] The type, characteristics, content, etc. of the specific lithium tetraborate contained in the second lithium-based solid electrolyte are the same as those described in the first embodiment, including preferred aspects thereof.
[0320] The second lithium-based solid electrolyte contains a lithium salt.
[0321] The type, characteristics, content, etc. of the lithium salt contained in the second lithium-based solid electrolyte are the same as those described in the first embodiment, including preferred aspects thereof.
[0322] The second lithium-based solid electrolyte contains the elements Li, B, and O because it contains specific lithium tetraborate.
[0323] Furthermore, the second lithium-based solid electrolyte further preferably contains a specific element selected from the group consisting of periodic table Group 4 elements, periodic table Group 15 elements, periodic table Group 16 elements, periodic table Group 17 elements, Si, C, Sc and Y.
[0324] Regarding the type of specific element contained in the second lithium-based solid electrolyte and the molar amount of Li, B, O and the specific element contained in the second lithium-based solid electrolyte, the preferred method is also included and is the same as described in the first embodiment.
[0325] The second lithium-based solid electrolyte may contain water, and preferably contains water.
[0326] The content of water contained in the second lithium-based solid electrolyte is preferably 45% by mass or less, more preferably 40% by mass or less, further preferably 35% by mass or less, particularly preferably 30% by mass or less, and most preferably 25% by mass or less relative to the total mass of the lithium-based solid electrolyte. In addition, the lower limit of the water content is not particularly limited, but is preferably 5% by mass or more, more preferably 10% by mass or more, further preferably 15% by mass or more, and particularly preferably 20% by mass or more relative to the total mass of the lithium-based solid electrolyte.
[0327] The water content is the same as that described in the first embodiment, and the method for measuring the water content is also the same as that described in the first embodiment.
[0328] The molar ratio and content of each component in the second lithium-based solid electrolyte can be obtained using a known method. For example, the content of each element in the second lithium-based solid electrolyte can be determined, and the molar ratio and content of each component can be determined based on the structure of the compound used. As a method of elemental analysis, for example, Na and B are analyzed by ICP-OES (Inductively coupled plasma optical emission spectrometry), N, etc. are analyzed by inert gas fusion method, and F and S are analyzed by combustion ion chromatography. Regarding O, the analysis mass of elements other than O can be added and calculated as a difference from the total amount of powder. In addition, the method for calculating the content of each element is not limited to the above. Considering the structure of the compound used, the content of other elements can be estimated based on the analysis results of the content of one element.
[0329] (Characteristics of lithium-based solid electrolytes)
[0330] TG-MS measurement
[0331] From the viewpoint of achieving a more excellent effect of the present invention, when thermogravimetry mass spectrometry (TG-MS) is performed on the molded body obtained by pressurizing the second lithium-based solid electrolyte, it is preferred to detect the component with a molecular weight of 18 in a temperature range exceeding 100°C, and it is more preferred to detect the component with a molecular weight of 18 in a temperature range exceeding 120°C.
[0332] The above characteristics are the same as those described in the first embodiment, and the measurement method is also the same as that described in the first embodiment.
[0333] · 7 Li-NMR measurements
[0334] From the viewpoint of further improving the effect of the present invention, the second lithium-based solid electrolyte was solidified at 120°C. 7 The full width at half maximum of the peak whose chemical shift appears in the range of -100 to +100 ppm in the spectrum obtained during Li-NMR measurement is 200 ppm higher than that of the solid state of the second lithium-based solid electrolyte at 20°C. 7 The ratio of the full width at half maximum of the peak whose chemical shift in the spectrum obtained during Li-NMR measurement appears in the range of -100 to +100 ppm is preferably 50% or less, more preferably 40% or less, and further preferably 35% or less. The lower limit is not particularly limited, but is 10% or more in most cases.
[0335] The full width at half maximum (FWHM) of a peak refers to the width (ppm) at a point (H / 2) that is 1 / 2 of the height (H) of the peak.
[0336] Furthermore, from the viewpoint of achieving a more excellent effect of the present invention, the solidification of the second lithium-based solid electrolyte is carried out at 20°C. 7 When the first peak in the spectrum obtained during Li-NMR measurement that appears in the range of -100 to +100 ppm is subjected to waveform separation, there is a second peak with a chemical shift in the range of -3 to 3 ppm and a half-peak width of 5 ppm or less, and the ratio of the area intensity of the second peak to the area intensity of the first peak is 0.5% or more. The ratio of the above-mentioned area intensity is more preferably 2% or more, and further preferably 15% or more. The upper limit of the ratio of the above-mentioned area intensity is not particularly limited, but in most cases it is 50% or less.
[0337] The above characteristics are the same as those described in the first embodiment, and the measurement method is also the same as that described in the first embodiment.
[0338] · 1 H-NMR measurements
[0339] From the viewpoint of achieving a more excellent effect of the present invention, it is preferred that the second lithium-based solid electrolyte 1 The chemical shift in the spectrum obtained by H-NMR measurement is within the range of -200 to +200 ppm, and both a sharp peak and a broad peak appear.
[0340] The above characteristics are the same as those described in the first embodiment, and the measurement method is also the same as that described in the first embodiment.
[0341] · 19 F-NMR measurements
[0342] From the viewpoint of achieving a more excellent effect of the present invention, when the lithium salt contains fluorine atoms, it is preferred to pass the second lithium-based solid electrolyte. 19The chemical shift in the spectrum obtained by F-NMR measurement showed a sharp peak in the range of -200 to +300 ppm.
[0343] The above characteristics are the same as those described in the first embodiment, and the measurement method is also the same as that described in the first embodiment.
[0344] TG-DTA measurement
[0345] Furthermore, from the viewpoint of achieving more excellent effects of the present invention, the mass reduction rate when the second lithium-based solid electrolyte is heated to 800° C. is preferably 20 to 40% by mass. Among them, from the viewpoint of achieving more excellent effects of the present invention, the mass reduction rate is more preferably 25 to 35% by mass.
[0346] The above characteristics are the same as those described in the first embodiment, and the measurement method is also the same as that described in the first embodiment.
[0347] Ionic conductivity
[0348] From the viewpoint of achieving a more excellent effect of the present invention, the ion conductivity of the molded body obtained by pressurizing the second lithium-based solid electrolyte at -10°C is preferably 1×10 -5 S / cm or more, more preferably 1×10 -4 S / cm or more. The upper limit is not particularly limited, but in many cases it is 1×10 -3 S / cm or less.
[0349] The above characteristics are the same as those described in the first embodiment, and the measurement method is also the same as that described in the first embodiment.
[0350] Infrared absorption spectrum
[0351] Furthermore, from the viewpoint of further improving the effect of the present invention, in the infrared absorption spectrum of the second lithium-based solid electrolyte, the wavelength of the second lithium-based solid electrolyte is 3000 to 3500 cm -1 The maximum absorption intensity in the wave number region is relatively large compared to that in the region of 800 to 1600 cm -1 The ratio of the maximum absorption intensity in the wave number region is preferably 1 / 5 or more. Among them, from the viewpoint of the better effect of the present invention, the above ratio is preferably 3 / 10 or more, more preferably 2 / 5 or more. The upper limit is not particularly limited, but is preferably 1 or less.
[0352] The above characteristics are the same as those described in the first embodiment, and the measurement method is also the same as that described in the first embodiment.
[0353] Raman spectroscopy
[0354] Furthermore, from the viewpoint of achieving a more excellent effect of the present invention, the second lithium-based solid electrolyte has a Raman spectrum of 600 to 850 cm -1 The coefficient of determination obtained by performing linear regression analysis using the least squares method in the wavenumber region is preferably 0.9400 or more.
[0355] In addition, from the viewpoint of achieving more excellent effects of the present invention, the coefficient of determination is more preferably 0.9600 or more. The upper limit is not particularly limited, but 1.0000 is exemplified.
[0356] The above characteristics are the same as those described in the first embodiment, and the measurement method is also the same as that described in the first embodiment.
[0357] Karl Fischer measurement
[0358] From the viewpoint of a more excellent effect of the present invention, after drying the molded body obtained by pressurizing the second lithium-based solid electrolyte by a prescribed method, when measuring the water content evaporated from the obtained molded body based on the Karl Fischer method, it is preferred that the water content B evaporated from the first lithium-based solid electrolyte during heating from room temperature to 200°C is greater than the water content A evaporated from the first lithium-based solid electrolyte during heating from room temperature (27°C) to 100°C.
[0359] The above characteristics are the same as those described in the first embodiment, and the measurement method is also the same as that described in the first embodiment.
[0360] ·Requirement T
[0361] Furthermore, from the viewpoint of achieving more excellent effects of the present invention, the second lithium-based solid electrolyte preferably satisfies requirement T. The following requirement T is the same as the requirement T defined in the first embodiment, and the measurement method is also the same as that described in the first embodiment.
[0362] Requirement T: In the Raman spectrum of lithium-based solid electrolytes, the -1 With a peak and a full width at half maximum of 5 cm -1 The first peak above is at 770-790cm -1 With a peak and a full width at half maximum of 5 cm -1 The second peak above 1020-1040cm -1 With a peak and a full width at half maximum of 5 cm -1 None of the above third peaks exist, or,
[0363] In the Raman spectrum, when at least one specific peak selected from the group consisting of a first peak, a second peak, and a third peak exists, a ratio to at least one intensity of the specific peak calculated by the following intensity measurement method is 5.0 or less.
[0364] Intensity measurement method: The 400-600 cm-1 Raman spectrum is -1 The minimum value M1 of the Raman intensity in the wave number region and the 1300-1500cm -1 The points of the minimum value M2 of the Raman intensity in the wave number region of 710-730 cm are connected to obtain a straight line, and in the region from the wave number indicating the above minimum value M1 to the wave number indicating the above minimum value M2, the peaks of the Raman intensity in the region of 710-730 cm are calculated. -1 、770~790cm -1 and 1020~1040cm -1 The average difference value between the Raman intensity of the above-mentioned straight line at each wavenumber in the area outside the area and the Raman intensity of the Raman spectrum is calculated, and the absolute value of the difference between the Raman intensity of the above-mentioned peak and the Raman intensity of the above-mentioned straight line at the wavenumber representing the peak top of the above-mentioned specific peak is calculated, and the ratio of the absolute value of the above-mentioned difference to the above-mentioned average difference value is set as the intensity ratio.
[0365] In the Raman spectrum of the above-mentioned lithium-based solid electrolyte, when the first peak, the second peak, and the third peak do not exist, or when a specific peak selected from the group including the first peak, the second peak, and the third peak exists, it is more preferred that at least one intensity ratio of the specific peak is 3.0 or less. Among them, when the first peak, the second peak, and the third peak do not exist, or when a specific peak selected from the group including the first peak, the second peak, and the third peak exists, it is further preferred that at least one intensity ratio of the specific peak is 2.0 or less, and it is particularly preferred that the first peak, the second peak, and the third peak do not exist.
[0366] ·Requirement X
[0367] From the viewpoint of achieving more excellent effects of the present invention, the second lithium-based solid electrolyte preferably satisfies the following requirement X. The following requirement X is the same as the requirement X defined in the first embodiment, and the measurement method is also the same as that described in the first embodiment.
[0368] Requirement X: In the reduced two-body distribution function G(r) obtained from the total X-ray scattering measurement of lithium-based solid electrolytes, there is a peak located at r. The first peak and the peak top in the range of r are The second peak in the range of , the peak G(r) of the first peak shows more than 1.0 (preferably more than 1.2), and the peak G(r) of the second peak shows more than 0.8 (preferably more than 1.0).
[0369] ·Requirement Y
[0370] From the viewpoint of achieving more excellent effects of the present invention, the second lithium-based solid electrolyte preferably satisfies the following requirement Y. The following requirement Y is the same as the requirement Y specified in the first embodiment, and the measurement method is also the same as that described in the first embodiment.
[0371] Requirement Y: In the X-ray diffraction pattern of the lithium-based solid electrolyte obtained from X-ray diffraction measurement using CuKα rays, there is no first peak with a peak top in the range of 21.6 to 22.0° and a full width at half maximum of 0.65° or less, no second peak with a peak top in the range of 25.4 to 25.8° and a full width at half maximum of 0.65° or less, no third peak with a peak top in the range of 33.4 to 33.8° and a full width at half maximum of 0.65° or less, and no fourth peak with a peak top in the range of 34.4 to 34.8° and a full width at half maximum of 0.65° or less, or
[0372] In the X-ray diffraction pattern, when there is at least one specific peak selected from the group consisting of a first peak, a second peak, a third peak and a fourth peak, at least one of the specific peaks has an intensity ratio calculated by the following intensity measurement method of 5.0 or less.
[0373] Intensity measurement method: The average intensity 1 in the range of +0.45° to +0.55° is calculated from the diffraction angle 2θ of the peak top of the specific peak, and the average intensity 2 in the range of -0.55° to -0.45° is calculated from the diffraction angle 2θ of the peak top of the specific peak, thereby calculating the arithmetic mean of the average intensity 1 and the average intensity 2, and the ratio of the peak intensity at the peak top of the specific peak to the arithmetic mean is set as the intensity ratio.
[0374] In the X-ray diffraction spectrum obtained from the X-ray diffraction measurement using CuKα rays of the second embodiment of the above-mentioned lithium-based solid electrolyte, when the first peak, the second peak, the third peak, and the fourth peak do not exist, or when a specific peak selected from the group including the first peak, the second peak, the third peak, and the fourth peak exists, it is more preferred that at least one intensity ratio of the specific peak is 3.0 or less. Among them, when the first peak, the second peak, the third peak, and the fourth peak do not exist, or when a specific peak selected from the group including the first peak, the second peak, the third peak, and the fourth peak exists, it is further preferred that at least one intensity ratio of the specific peak is 2.0 or less.
[0375] exist Fig.15 In FIG. 1 , an example of calculation results of the lithium-based solid electrolyte included in the present invention based on the first principle molecular dynamics (MD) method is shown. Fig.15 In the example, Li(FSO 2 ) 2 The arrangement of each atom of Li, S, F, H, B, O and N contained in the lithium-based solid electrolyte of the present invention (first embodiment and second embodiment) of N (hereinafter also referred to as "LiFSI"). In addition, the dotted lines in the figure represent hydrogen bonds, Coulomb forces, etc.
[0376] Think Fig.15 As shown, in the lithium-based solid electrolyte of the present invention, a region containing water (H 2 O) and the ion conduction path of the anions contained in LiSFI (the area shown in A2 in the figure). Fig.15 As shown, in the BO 3 -BO 4 In the connection structure, BO present on the particle surface 3 Structure and BO 4 Part of the structure with H 2 O interacts with each other and takes on a part of the above-mentioned ion conduction path.
[0377] In addition, BO present on the particle surface 3 Structure and BO 4 A portion of the structure may have, for example, a dangling bond caused by an element defect.
[0378] In addition, the BO present on the particle surface can also 3 Structure and BO 4 Part of the structure with H 2 O to form a B-OH partial structure. It is believed that the B-OH partial structure undertakes a part of the ion conduction path. In addition, it is believed that the B-OH partial structure improves the dispersibility in water in the steps 2, 2A, 2B, and 2C in the method for producing the lithium-based solid electrolyte described later.
[0379] Furthermore, it is believed that in the presence of Li and water (H 2 O) strongly interact (the Li-O bond distance is calculated to be about ), Coulomb force acts strongly to bind water, which is believed to contribute to solidification.
[0380] In addition, water (H 2The structures and numbers of O) and LiSFI are calculated based on virtual settings and are not limited to these.
[0381] In the above ion conduction path, except for H 2 In addition to the anions contained in LiSFI and O, other components may be contained. As other components, for example, BO contained in the specific lithium tetraborate particles may be 3 -BO 4 Connection structure, can also be with BO 3 -BO 4 The molecules of different structures are connected. As the molecules of different structures, for example, B(OH) 3 、B(OH) 4 - and BO present in lithium tetraborate crystals 3 -BO 4 The connection structure can consider BOs with different structures or number of connections 3 -BO 4 As mentioned above, the H contained in the above ion conduction path 2 A part of O may be in a dissociated state.
[0382] In the above ion conduction path, H 2 O, the anions contained in LiSFI and the above-mentioned other components (if present) form a pseudo-crosslinked structure or a three-dimensional structure based on chemical reactions through hydrogen bonds, etc. As a result, it is believed that the lithium-based solid electrolyte develops in the direction of pseudo-solidification or solidification.
[0383] In addition, it is considered that when forming the pseudo cross-linked structure or the three-dimensional structure as described above, the presence of BO 4 .
[0384] The above description is based on an inference based on calculation results performed on a specific lithium-based solid electrolyte included in the present invention, and the present invention is not limited to the contents described above.
[0385] <<Method for producing lithium-based solid electrolyte>>
[0386] The method for producing the lithium-based solid electrolyte of the present invention (first embodiment and second embodiment) is not particularly limited, but from the viewpoint of being able to produce the lithium-based solid electrolyte of the present invention with good productivity, a production method including the following steps 1A to 3A is preferred.
[0387] Step 1A: A step of mechanically grinding a lithium oxide containing Li and B (preferably lithium tetraborate) in the presence of a lithium salt
[0388] Step 2A: Step of mixing the product obtained in step 1A with water
[0389] Step 3A: Step of removing water from the dispersion obtained in step 2A to obtain a lithium-based solid electrolyte
[0390] Hereinafter, the steps of the above-mentioned manufacturing method will be described in detail.
[0391] Step 1A is a step of subjecting the lithium-based oxide (preferably lithium tetraborate) to mechanical milling in the presence of a lithium salt.
[0392] Hereinafter, the materials used in this step 1A will be described in detail, and then the steps will be described in detail.
[0393] Examples of the lithium salt include lithium salts containing one or more of the above-mentioned specific elements, preferably lithium salts containing two or more of the specific elements, and more preferably compounds represented by formula (1).
[0394] Formula (1) LiN(R f1 SO 2 )(R f2 SO 2 )
[0395] R f1 and R f2 Each independently represents a halogen atom or a perfluoroalkyl group.
[0396] R f1 and R f2 In the case of a perfluoroalkyl group, the number of carbon atoms in the perfluoroalkyl group is not particularly limited.
[0397] R f1 and R f2 It is preferably a halogen atom or a perfluoroalkyl group having 1 to 6 carbon atoms, more preferably a halogen atom or a perfluoroalkyl group having 1 to 2 carbon atoms, and still more preferably a halogen atom. If the volume of the terminal group increases, the steric hindrance increases, which becomes a factor that hinders ion conduction. Therefore, R f1 and R f2 In the case of a perfluoroalkyl group, the one having a smaller number of carbon atoms is preferred.
[0398] Below, lithium salts are exemplified.
[0399] (L-1) Inorganic lithium salt: LiPF 6 , LiBF 4 、LiAsF 6 and LiSbF 6 Inorganic fluoride salts such as LiClO 4 、LiBrO 4 and LiIO 4Etc. High halogen acid salts; LiAlCl 4 And other inorganic chloride salts.
[0400] (L-2) Fluorine-containing organic lithium salt: LiCF 3 SO 3 Perfluoroalkyl sulfonates; LiN(CF 3 SO 2 ) 2 、LiN(CF 3 CF 2 SO 2 ) 2 、1,1,2,2,3,3-hexafluoropropane-1,3-disulfonylimide lithium、LiN(FSO 2 ) 2 and LiN(CF 3 SO 2 )(C 4 F 9 SO 2 ) and other perfluoroalkylsulfonyl imide salts; LiC(CF 3 SO 2 ) 3 Perfluoroalkylsulfonylmethyl salts; Li[PF 5 (CF 2 CF 2 CF 3 )]、Li[PF 4 (CF 2 CF 2 CF 3 ) 2 ]、Li[PF 3 (CF 2 CF 2 CF 3 ) 3 ]、Li[PF 5 (CF 2 CF 2 CF 2 CF 3 )]、Li[PF 4 (CF 2 CF 2 CF 2 CF 3 ) 2 ] and Li[PF 3 (CF 2 CF 2 CF 2 CF 3 ) 3 ] and other fluoroalkyl fluorophosphates.
[0401] (L-3) Oxalate borate: lithium bis(oxalato)borate and lithium difluorooxalatoborate.
[0402] In addition to the above, LiF, LiCl, LiBr, LiI, Li 2 SO 4 、LiNO 3 , Li 2 CO 3 , CH 3 COOLi、LiAsF 6 、LiSbF 6 、LiAlCl 4 and LiB(C 6 H 5 ) 4 wait.
[0403] Among them, LiPF is preferred 6 , LiBF 4 、LiAsF 6 、LiSbF 6 、LiClO 4 、Li(R f1 SO 3 )、LiN(R f1 SO 2 ) 2 、LiN(FSO 2 ) 2 、LiN(R f1 SO 2 )(R f2 SO 2 ), LiCl, LiB or LiI, more preferably LiPF 6 , LiBF 4 、LiN(R f1 SO 2 ) 2 、LiN(FSO 2 ) 2 or LiN(R f1 SO 2 )(R f2 SO 2 ).
[0404] Here, R f1 and R f2 Each independently represents a perfluoroalkyl group.
[0405] The amount of the lithium salt used is not particularly limited, and the amount used is appropriately adjusted so as to obtain the above-mentioned lithium-based solid electrolyte of the present invention.
[0406] The amount of the lithium salt used is preferably 1 to 300 parts by mass, more preferably 100 to 200 parts by mass, based on 100 parts by mass of the lithium-based oxide.
[0407] Examples of lithium-based oxides containing Li and B include Li 2 B 4 O 7 、LiBO 5 , LiB 3 O 5 , Li 3 B 11 O 18 , Li 2 B 7 O 12 , LiB 2 O 3 (OH)H 2 O. Li 4 B 8 O 13 (OH) 2 (H 2 O) 3 , Li 4 B 7 O 12 Cl and Li 3 B 7 O 12 Among them, Li is preferred 2 B 4 O 7 (lithium tetraborate).
[0408] In order to expand the potential window when a lithium solid electrolyte is used as a battery, a liquid selected from the group consisting of an organic solvent and an ionic liquid may be used in addition to water and a Li salt.
[0409] Examples of the organic solvent include acetamide, acetonitrile, ethylene carbonate, vinylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate, 1,2-dimethoxyethane, tetrahydrofuran, γ-butyrolactone, fluoroethylene carbonate, and 1,3-propane sultone.
[0410] Examples of the ionic liquid include imidazolium, pyrrolidinium, piperidinium, ammonium, 1-ethyl-3-methylimidazolium, diethylmethyl-2-methoxyethylammonium, N-methyl-N-propylpiperidinium, N-methyl-N-propylpyridinium, 1-butyl-1-2,3-dimethylimidazolium, 1-methyltetrahydrothiophenium, 1-ethyltetrahydrothiophenium, ethylmethylpropylsulfonium, butyldimethylsulfonium, 1-propyltetrahydrothiophenium, 1-methyl[1,4]-sulfoxonium, 1-butyltetrahydrothiophenium, diethylethylsulfonium, 1-propyl-2,3,5-trimethylpyrazolium, bistrifluoromethylsulfonamide, dicyanamide, hexafluorophosphate, and tetrachloroaluminate.
[0411] Mechanical grinding is a process of pulverizing a sample while applying mechanical energy to the sample.
[0412] As mechanical grinding treatment, for example, a ball mill, a vibration mill, a turbine mill and a disc mill can be mentioned, and from the viewpoint of being able to manufacture the lithium-based solid electrolyte of the present invention with good productivity, a ball mill is preferred. As a ball mill, for example, a vibration ball mill, a rotary ball mill and a planetary ball mill can be mentioned, and a planetary ball mill is more preferred.
[0413] As the conditions for the ball milling treatment, appropriate conditions can be selected according to the raw materials used.
[0414] There is no particular restriction on the material of the grinding balls (media) used in ball milling. For example, agate, silicon nitride, stabilized zirconia (YSZ), alumina and iron-based alloys can be mentioned. From the perspective of being able to manufacture the lithium-based solid electrolyte of the present invention with good productivity, stabilized zirconia (YSZ) is preferred.
[0415] The average particle size of the grinding balls is not particularly limited, but from the viewpoint of being able to manufacture the lithium-based solid electrolyte of the present invention with good productivity, it is preferably 1 to 10 mm, and more preferably 3 to 7 mm. The above average particle size is a value obtained by measuring the diameters of 50 random grinding balls and calculating the average of these. In the case where the grinding balls are not spherical, the major diameter is set as the diameter.
[0416] The number of grinding balls used in ball milling is not particularly limited, but is preferably 10 to 100, more preferably 40 to 60, from the viewpoint of being able to produce the lithium-based solid electrolyte of the present invention with good productivity.
[0417] There is no particular restriction on the material of the grinding pot used in ball milling. For example, agate, silicon nitride, stabilized zirconia (YSZ), aluminum oxide and iron alloys can be mentioned. From the perspective of being able to manufacture the lithium-based solid electrolyte of the present invention with good productivity, stabilized zirconia (YSZ) is preferred.
[0418] The rotation speed during ball milling is not particularly limited, but is preferably 200 to 700 rpm, more preferably 350 to 550 rpm, from the viewpoint of being able to produce the lithium-based solid electrolyte of the present invention with good productivity.
[0419] The treatment time of ball milling is not particularly limited, but is preferably 10 to 200 hours, more preferably 20 to 140 hours, from the viewpoint of being able to produce the lithium-based solid electrolyte of the present invention with good productivity.
[0420] The ball milling may be performed in the air or in an inert gas (eg, argon, helium, or nitrogen) atmosphere.
[0421] Step 2A is a step of mixing the product obtained in step 1A with water. By performing this step, the lithium-based oxide containing Li and B obtained in step 1A and subjected to mechanical milling treatment and water are mixed to generate the lithium-based solid electrolyte of the present invention containing a large amount of O (oxygen element).
[0422] It is believed that in step 2A, a composition with good manufacturing suitability can be obtained by preparing a mixed solution including a mechanically milled lithium oxide and water, and the water content is increased by forcibly adsorbing water on the mechanically milled lithium oxide, thereby improving ion conductivity.
[0423] The amount of water used is not particularly limited, but from the viewpoint of achieving more excellent effects of the present invention, the amount of water used is preferably 10 to 200 parts by mass, more preferably 50 to 150 parts by mass, based on 100 parts by mass of the product obtained in step 1A.
[0424] The method for mixing the product obtained in step 1A and water is not particularly limited, and the products may be mixed all at once, or water may be added stepwise to the product obtained in step 1A and mixed.
[0425] During the mixing, ultrasonic treatment may be performed as necessary.
[0426] The time of the ultrasonic treatment is not particularly limited, but is preferably 10 minutes to 5 hours from the viewpoint of achieving more excellent effects of the present invention.
[0427] Step 3A is a step of removing water from the dispersion obtained in step 2A to obtain a lithium-based solid electrolyte.
[0428] In this process, water contained in the dispersion is removed to obtain a lithium-based solid electrolyte containing water. In this process, water can be removed from the dispersion in such a way that a lithium-based solid electrolyte is formed and water remains in the lithium-based solid electrolyte. Specifically, water can be removed in such a way that water in the above-mentioned first to fourth states at least remains in the lithium-based solid electrolyte. In addition, water can be removed in such a way that water in the second to fourth states at least remains in the lithium-based solid electrolyte, water can be removed in such a way that water in the third to fourth states at least remains in the lithium-based solid electrolyte, or water can be removed in such a way that water in the fourth state at least remains in the lithium-based solid electrolyte.
[0429] That is, in the above step 3A, in order to obtain the above-mentioned lithium-based solid electrolyte containing water, a part of the water in the dispersion may be removed to obtain a predetermined lithium-based solid electrolyte.
[0430] The method for removing water from the dispersion obtained in step 2A is not particularly limited, and water can be evaporated by heating or by vacuum drying. By adjusting the amount of water removed within the above range, the water content contained in the lithium-based solid electrolyte can be appropriately adjusted.
[0431] As this process, it is preferred to dry the above dispersion under vacuum conditions to obtain a lithium-based solid electrolyte containing water. Vacuum conditions refer to drying treatment under a specified reduced pressure environment and at a specified temperature. As more specific vacuum conditions, for example, less than 2000Pa (preferably less than 200Pa, more preferably less than 20Pa) and less than 60°C (preferably less than 40°C) can be cited. There is no particular restriction on the lower limit of the above pressure, for example, it is greater than 10Pa. In addition, there is no particular restriction on the lower limit of the above temperature, for example, it is greater than 0°C.
[0432] The treatment time of the vacuum drying treatment may be appropriately selected according to the pressure and temperature, the amount of water contained in the dispersion, the desired moisture content of the lithium-based solid electrolyte, etc., and is, for example, 120 to 1080 minutes, preferably 300 to 900 minutes.
[0433] Furthermore, before the step 1A, a step 0 of mechanically polishing the lithium-based oxide (preferably lithium tetraborate) may be performed in an environment without the presence of a lithium salt.
[0434] A preferred embodiment of the mechanical polishing treatment performed in step 0 is the same as a preferred embodiment of the mechanical polishing treatment performed in step 1A described above.
[0435] As another preferred embodiment of the method for producing the lithium-based solid electrolyte of the present invention, a production method including the following steps 1B to 3B is preferred.
[0436] Step 1B: a step of subjecting a lithium oxide (preferably lithium tetraborate) to mechanical grinding
[0437] Step 2B: Step of mixing the product obtained in step 1B, water and lithium salt
[0438] Step 3B: Step of removing water from the dispersion obtained in step 2B to obtain a lithium-based solid electrolyte
[0439] The difference between step 1B and step 1A is that, in step 1A, the mechanical milling treatment is carried out in the presence of a lithium salt, whereas in step 1B, the mechanical milling treatment is carried out without using a lithium salt.
[0440] A preferred embodiment of the mechanical polishing treatment performed in step 1B is the same as a preferred embodiment of the mechanical polishing treatment performed in step 1A.
[0441] The difference between step 2B and step 2A is as follows: in step 2B, the product obtained in step 1B, water and a lithium salt are mixed.
[0442] The lithium salt used in step 2B is the same as the lithium salt used in step 1A.
[0443] The amount of the lithium salt used in step 2B is preferably 1 to 300 parts by mass, more preferably 100 to 200 parts by mass, based on 100 parts by mass of the product obtained in step 1B.
[0444] The steps of step 2B are not particularly limited, and may be a method of mixing the product obtained in step 1B, water, and a lithium salt all together (method 1), a method of mixing the product obtained in step 1B and water to prepare a dispersion, and then mixing the obtained dispersion with a lithium salt (method 2), or a method of mixing the product obtained in step 1B and water to prepare a dispersion 1, mixing a lithium salt and water to prepare a solution 2, and then mixing the dispersion 1 and the solution 2 (method 3). When mixing the product obtained in step 1B and water, a dispersion treatment such as an ultrasonic treatment may be appropriately performed.
[0445] Among them, method 3 is preferred from the viewpoint of achieving more excellent effects of the present invention.
[0446] In method 2, when the dispersion obtained by mixing the product obtained in step 1B and water and the lithium salt are mixed, if the amount of the lithium salt is too much, the obtained liquid is easily gelled, and it is difficult to increase the mixing amount of the lithium salt. In contrast, in method 3, even if the product obtained in step 1B and the lithium salt are mixed in approximately equimolar amounts, the liquid is not easily gelled, and it is easy to increase the mixing amount of the lithium salt.
[0447] Step 3B is the same as step 3A.
[0448] As another preferred embodiment of the method for producing the lithium-based solid electrolyte of the present invention, a production method including the following steps 1C to 3C is preferred.
[0449] Step 1C: a step of subjecting a lithium oxide (preferably lithium tetraborate) to mechanical grinding
[0450] Step 2C: Step of mixing the product obtained in step 1C with water
[0451] Step 3C: A step of mixing a product obtained by removing water from the dispersion obtained in step 2C with a lithium salt to obtain a lithium-based solid electrolyte
[0452] Step 1C is the same as step 1B.
[0453] Step 2C is the same as step 2A.
[0454] The difference between step 3C and step 3A is that the product obtained by removing water from the dispersion obtained in step 2C and the lithium salt are mixed. In step 3C, the method for removing water from the dispersion obtained in step 2C is the same as that in step 3A, including a preferred embodiment.
[0455] The lithium salt used in step 3C is the same as the lithium salt used in step 1A.
[0456] The amount of the lithium salt used in step 3C is preferably 1 to 300 parts by mass, more preferably 100 to 200 parts by mass, based on 100 parts by mass of the product obtained by removing water from the dispersion obtained in step 2C.
[0457] The method of mixing the product obtained by removing water from the dispersion obtained in step 2C and the lithium salt is not particularly limited, and may be a method of immersing a solution obtained by dissolving the lithium salt in water in the product and mixing the two.
[0458] That is, a preferred embodiment of the method for producing the lithium-based solid electrolyte of the present invention comprises:
[0459] Step 1, subjecting a lithium oxide (more preferably lithium tetraborate) to mechanical grinding;
[0460] Step 2, mixing the product obtained in step 1 and water; and
[0461] Step 3, removing water from the dispersion obtained in step 2 to obtain a lithium-based solid electrolyte,
[0462] The production method that satisfies any one of the following requirements 1 to 3 can be mentioned.
[0463] Requirement 1: The mechanical milling treatment in step 1 is performed in the presence of a lithium salt containing one or more of the above-mentioned specific elements.
[0464] Requirement 2: In step 2, the product, water, and a lithium salt containing one or more of the above-mentioned specific elements are mixed.
[0465] Requirement 3: In step 3, a product obtained by removing water from the dispersion obtained in step 2 and a lithium salt containing one or more of the above-mentioned specific elements are mixed to obtain a lithium-based solid electrolyte.
[0466] Preferred embodiments of the treatments to be performed in each step and the components to be used are as described above.
[0467] <Dispersion liquid>
[0468] The dispersion of the present invention comprises the lithium-based solid electrolyte of the present invention and a solvent (eg, an organic solvent, water). The dispersion of the present invention is in liquid form and can be applied to various objects to be coated, and can be used to produce a solid electrolyte layer.
[0469] In the present specification, the dispersion of the present invention refers to an embodiment in which the content of the solvent in the dispersion is 80% by mass or more.
[0470] The dispersion of the present invention may contain other components in addition to the lithium-based solid electrolyte of the present invention and the solvent.
[0471] As other components, a binder can be mentioned.
[0472] Examples of the binder include various organic high molecular compounds (polymers).
[0473] The organic polymer compound constituting the binder may be in a particulate form or may be in a non-particulate form.
[0474] Furthermore, as other components, other solid electrolytes other than the lithium-based solid electrolyte of the present invention can be cited. Other solid electrolytes refer to solid electrolytes that enable ions to move inside them. As solid electrolytes, inorganic solid electrolytes are preferred.
[0475] Examples of other solid electrolytes include sulfide-based inorganic solid electrolytes, oxide-based inorganic solid electrolytes, halide-based inorganic solid electrolytes, and hydride-based solid electrolytes.
[0476] The method for producing the dispersion of the present invention is not particularly limited, and examples thereof include a method comprising the above-mentioned steps 1A and 2A and a method comprising steps 1B and 2B.
[0477] <Application>
[0478] The lithium-based solid electrolyte of the present invention shows excellent ion conductivity, so it can be applied to various purposes. The lithium-based solid electrolyte of the present invention can be used in various batteries (for example, all-solid-state secondary batteries, solid oxide fuel cells, solid oxide water vapor electrolysis). Among them, the lithium-based solid electrolyte of the present invention is preferably used in all-solid-state lithium-ion secondary batteries.
[0479] More specifically, the lithium-based solid electrolyte of the present invention is preferably used to form a solid electrolyte contained in at least any one of the positive electrode active material layer, the solid electrolyte layer and the negative electrode active material layer in an all-solid-state secondary battery. Among them, the lithium-based solid electrolyte of the present invention is preferably used to form a solid electrolyte contained in the positive electrode active material layer, the solid electrolyte layer and the negative electrode active material layer in an all-solid-state lithium-ion secondary battery. In addition, the lithium-based solid electrolyte of the present invention is preferably used as a solid electrolyte contained in any one of the positive electrode active material layer, the solid electrolyte layer and the negative electrode active material layer in an all-solid-state lithium-ion secondary battery.
[0480] Furthermore, the lithium-based solid electrolyte of the present invention can be preferably used as a coating material for coating the surface of the positive electrode active material. That is, as one of the preferred embodiments of the present invention, a modified positive electrode active material can be cited, which has a positive electrode active material and a coating layer disposed on the positive electrode active material, and the coating layer includes the lithium-based solid electrolyte of the present invention.
[0481] In addition, the lithium-based solid electrolyte of the present invention is preferably used as a coating material for coating the surface of the negative electrode active material. That is, as one of the preferred embodiments of the present invention, a modified negative electrode active material can be cited, which has a negative electrode active material and a coating layer disposed on the negative electrode active material, and the coating layer includes the lithium-based solid electrolyte of the present invention.
[0482] When the lithium-based solid electrolyte of the present invention is used, it is preferred that the lithium-based solid electrolyte of the present invention be subjected to a pressure treatment and molded into a predetermined shape before use.
[0483] The method of the pressure treatment is not particularly limited, and examples thereof include a method using a known pressure device.
[0484] The pressure applied during the pressurization treatment is not particularly limited, and the optimal pressure can be appropriately selected. However, from the viewpoint of achieving more excellent effects of the present invention, the pressure is preferably 5 to 1500 MPa, and more preferably 10 to 600 MPa.
[0485] The time of the pressurization treatment is not particularly limited, but is preferably 1 second to 0.5 hour, more preferably 2 seconds to 0.2 hour, from the viewpoint of more excellent effects of the present invention and productivity.
[0486] Furthermore, during the pressurization treatment, a heat treatment may be performed. The heating temperature during the heat treatment is not particularly limited, but is preferably 40 to 400° C., more preferably 50 to 350° C. The heating time during the heat treatment is preferably 1 minute to 6 hours.
[0487] The atmosphere during pressurization is not particularly limited, and examples thereof include atmospheric air, dry air (dew point -20°C or lower), and an inert gas (for example, argon, helium, and nitrogen) atmosphere.
[0488] The ion conductivity (27° C.) of the lithium-based solid electrolyte of the present invention is not particularly limited, but is preferably 1.0×10 -5 S / cm or more, more preferably 1.0×10 -4 S / cm or more. The upper limit is not particularly limited, but is often 1.0×10 -2 S / cm or less.
[0489] The dispersion liquid of the present invention containing the lithium-based solid electrolyte of the present invention can be preferably used as a dispersion liquid for forming a solid electrolyte layer.
[0490] The method for forming a solid electrolyte layer using the above-mentioned solid electrolyte layer forming dispersion is not particularly limited, but a method for forming a solid electrolyte layer by applying the solid electrolyte layer forming dispersion to an object can be cited. In addition, as required, the formed coating film can be subjected to a pressure treatment.
[0491] The coating method of the solid electrolyte layer-forming dispersion is not particularly limited, and examples thereof include spray coating, spin coating, dip coating, slit coating, spray coating, aerosol deposition, thermal spraying, and bar coating.
[0492] In addition, after applying the dispersion for forming a solid electrolyte layer, the obtained coating film may be dried as needed. The drying temperature is not particularly limited, but as a lower limit, it is preferably 30°C or more, more preferably 60°C or more, and further preferably 80°C or more. As an upper limit of the drying temperature, it is preferably 300°C or less, and more preferably 250°C or less.
[0493] The method of pressurizing the coating film is not particularly limited, but a method using a known pressurizing device (for example, a hydraulic cylinder press) can be mentioned.
[0494] The pressure applied during the pressurization treatment is not particularly limited, but is preferably 5 to 1500 MPa, more preferably 300 to 600 MPa, from the viewpoint of obtaining a more excellent ion conductivity of the formed solid electrolyte layer.
[0495] The time of the pressurization treatment is not particularly limited, but is preferably 1 minute to 6 hours, more preferably 1 to 20 minutes, from the viewpoint of better ion conductivity of the formed solid electrolyte layer and productivity.
[0496] Furthermore, during the pressurization treatment, a heat treatment may be performed. The heating temperature during the heat treatment is not particularly limited, but is preferably 30 to 300° C., and the heating time is more preferably 1 minute to 6 hours.
[0497] The atmosphere during pressurization is not particularly limited, and examples thereof include atmospheric air, dry air (dew point -20°C or lower), and an inert gas (for example, argon, helium, and nitrogen) atmosphere.
[0498] The lithium-based solid electrolyte of the present invention is also preferably used as a component of an electrode-forming composition. That is, the electrode-forming composition of the present invention is preferably a composition containing the lithium-based solid electrolyte of the present invention and an active material.
[0499] There is no particular restriction on the mixing ratio of the lithium-based solid electrolyte and the active material in the electrode forming composition, but there is no particular restriction on the content ratio of the lithium-based solid electrolyte to the active material (mass of the lithium-based solid electrolyte / mass of the active material), but it is preferably 0.01 to 50, and more preferably 0.05 to 20.
[0500] The lithium-based solid electrolyte contained in the electrode-forming composition is as described above.
[0501] Examples of the active material include negative electrode active materials and positive electrode active materials. The active material will be described in detail below.
[0502] (Negative electrode active material)
[0503] The negative electrode active material is preferably a material that can reversibly insert and release lithium ions. The negative electrode active material is not particularly limited, and examples thereof include carbonaceous materials, oxides of metal elements or semi-metal elements, lithium monomers, lithium alloys, and negative electrode active materials that can form alloys with lithium.
[0504] The carbonaceous material used as the negative electrode active material refers to a material substantially composed of carbon, for example, carbonaceous materials made of various synthetic resins such as calcined petroleum pitch, carbon black such as acetylene black (AB), graphite (natural graphite and artificial graphite such as vapor-grown graphite), and PAN (polyacrylonitrile) resin or furfuryl alcohol resin.
[0505] In addition, various carbon fibers such as PAN-based carbon fibers, cellulose-based carbon fibers, pitch-based carbon fibers, vapor-grown carbon fibers, dehydrated PVA (polyvinyl alcohol)-based carbon fibers, lignin carbon fibers, glassy carbon fibers, and activated carbon fibers, as well as intermediate phase microspheres, graphite whiskers, and flat graphite can also be cited.
[0506] These carbonaceous materials can be further divided into hardly graphitizable carbonaceous materials (also called hard carbon) and graphite-based carbonaceous materials according to the degree of graphitization.
[0507] Furthermore, the carbonaceous material preferably has the interplanar spacing, density or crystallite size described in Japanese Patent Laid-Open No. 62-022066, Japanese Patent Laid-Open No. 2-006856 and Japanese Patent Laid-Open No. 3-045473. The carbonaceous material need not be a single material, and a mixture of natural graphite and artificial graphite described in Japanese Patent Laid-Open No. 5-090844 and graphite with a coating layer described in Japanese Patent Laid-Open No. 6-004516 can also be used.
[0508] As the carbonaceous material, hard carbon or graphite is preferred, and graphite is more preferred.
[0509] The oxide of the metal element or semi-metal element used as the negative electrode active material is not particularly limited as long as it is an oxide that can occlude and release lithium, and examples thereof include oxides of metal elements (metal oxides), composite oxides of metal elements, composite oxides of metal elements and semi-metal elements, and oxides of semi-metal elements (semi-metal oxides). In addition, composite oxides of metal elements and composite oxides of metal elements and semi-metal elements are collectively referred to as metal composite oxides.
[0510] As these oxides, amorphous oxides are preferred, and chalcogenides which are reaction products of metal elements and elements of Group 16 of the periodic table are also preferred.
[0511] In the present invention, semimetallic elements refer to elements showing properties between metal elements and non-semimetallic elements, and generally include six elements of boron, silicon, germanium, arsenic, antimony and tellurium, and also include three elements of selenium, polonium and astatine.
[0512] Furthermore, amorphous means that, by X-ray diffraction using CuKα rays, a broad scattering band having a vertex in a region of 20 to 40° in 2θ values may also have crystalline diffraction lines. It is preferred that the strongest intensity of the crystalline diffraction lines seen in a region of 40 to 70° in 2θ values is 100 times or less, more preferably 5 times or less, and further preferably a diffraction line having no crystalline diffraction line intensity at the vertex of the broad scattering band seen in a region of 20 to 40° in 2θ values.
[0513] Among the compound group consisting of the above-mentioned amorphous oxides and chalcogenides, amorphous oxides of semimetallic elements or the above-mentioned chalcogenides are more preferred, and (complex) oxides or chalcogenides consisting of a single element or a combination of two or more elements selected from Groups 13 (IIIB) to 15 (VB) of the periodic table (for example, Al, Ga, Si, Sn, Ge, Pb, Sb and Bi) are further preferred.
[0514] As the amorphous oxide and chalcogenide, Ga is preferred. 2 O 3 、GeO、PbO、PbO 2 , Pb 2 O 3 , Pb 2 O 4 , Pb 3 O 4 , Sb 2 O 3 , Sb 2 O 4 , Sb 2 O 8 Bi 2 O 3 , Sb 2 O 8 Si 2 O 3 , Sb 2 O 5 、Bi 2 O 3 、Bi 2 O 4 、GeS、PbS、PbS 2 , Sb 2 S 3 or Sb 2 S 5 .
[0515] As negative electrode active materials that can be used together with the amorphous oxide negative electrode active material centered on Sn, Si or Ge, carbonaceous materials, lithium monomers, lithium alloys, or negative electrode active materials that can alloy with lithium that can occlude and / or release lithium ions or lithium metal are preferred.
[0516] From the viewpoint of high current density charge and discharge characteristics, the oxide of a metal element or a semi-metal element (particularly a metal (complex) oxide) and the above-mentioned chalcogenide preferably contain at least one of titanium and lithium as a constituent component.
[0517] Examples of the metal composite oxide containing lithium (lithium composite metal oxide) include composite oxides of lithium oxide and the above-mentioned metal oxides, the above-mentioned metal composite oxides or the above-mentioned chalcogenides. More specifically, examples include Li2 SnO 2 。
[0518] The negative electrode active material (e.g., metal oxide) preferably contains titanium element (titanium oxide) as well. Specifically, since the volume change during the occlusion and release of lithium ions is small, the fast charge-discharge characteristics are excellent. From the viewpoint of improving the life of the all-solid-state lithium ion secondary battery with suppressed electrode deterioration, Li 4 Ti 5 O 12 (lithium titanate [LTO]) is preferred. Also, as the negative electrode active material containing the preferred titanium element, TiNb 2 O 7 (titanium-niobium oxide [TNO]) can also be mentioned.
[0519] Regarding the lithium alloy as the negative electrode active material, there is no particular limitation as long as it is an alloy commonly used as the negative electrode active material of the all-solid-state lithium ion secondary battery. For example, a lithium-aluminum alloy can be mentioned.
[0520] The negative electrode active material capable of forming an alloy with lithium has no particular limitation as long as it is a material commonly used as the negative electrode active material of the all-solid-state lithium ion secondary battery. As the above negative electrode active material, a negative electrode active material (alloy) containing a silicon element or a tin element, and various metals such as Al and In can be mentioned. A negative electrode active material containing a silicon element (active material containing a silicon element) capable of achieving a higher battery capacity is preferred, and an active material containing a silicon element with a silicon element content of 50 mol% or more of all constituent elements is more preferred.
[0521] Generally, a negative electrode containing these negative electrode active materials (e.g., a Si negative electrode containing an active material containing a silicon element, a Sn negative electrode containing an active material containing a tin element) can occlude more Li ions compared to a carbon negative electrode (graphite, acetylene black, etc.). That is, the occlusion amount of Li ions per unit mass increases. Therefore, the battery capacity can be increased. As a result, it has the advantage of being able to further extend the battery driving time.
[0522] As the active material containing a silicon element, for example, silicon materials such as Si and SiOx (0 < x ≤ 1) can be mentioned, and further, silicon-containing alloys containing titanium, vanadium, chromium, manganese, nickel, copper, or lanthanum (e.g., LaSi 2 、VSi 2 、La-Si、Gd-Si, and Ni-Si) or organized active materials (e.g., LaSi 2 / Si) can be mentioned. In addition, SnSiO 3 and SnSiS 3In addition, SiOx can be used as a negative electrode active material (semi-metallic oxide) by itself, and Si is generated by the operation of the all-solid-state lithium-ion secondary battery, so it can be used as a negative electrode active material (precursor material) that can be alloyed with lithium.
[0523] Examples of the negative electrode active material containing tin include Sn, SnO, SnO 2 、SnS、SnS 2 And the active substances of the above silicon and tin elements.
[0524] From the viewpoint of battery capacity, the negative electrode active material is preferably a negative electrode active material that can alloy with lithium, more preferably the above-mentioned silicon material or an alloy containing silicon (alloy containing silicon element), and further preferably silicon (Si) or an alloy containing silicon.
[0525] The shape of the negative electrode active material is not particularly limited, but preferably particulate. The volume average particle size of the negative electrode active material is not particularly limited, but preferably 0.1 to 60 μm, more preferably 0.5 to 20 μm, and further preferably 1.0 to 15 μm.
[0526] The volume average particle size is measured by the following procedure.
[0527] Use water (heptane in the case of unstable substances in water) to dilute the negative electrode active material in a 20 mL sample bottle to prepare a 1% dispersion. The diluted dispersion sample was irradiated with 1 kHz ultrasound for 10 minutes and then used in the test immediately. Using the dispersion sample and using a laser diffraction / scattering particle size distribution measuring device, 50 data readings were performed using a measuring quartz cell at a temperature of 25°C to obtain the volume average particle size. For other detailed conditions, refer to JIS Z 8828:2013 "Particle Size Analysis-Dynamic Light Scattering Method" as needed. Make 5 samples for each level and use their average value.
[0528] The negative electrode active material may be used alone or in combination of two or more.
[0529] The surface of the negative electrode active material may also be coated with another metal oxide.
[0530] As the surface coating agent, metal oxides containing Ti, Nb, Ta, W, Zr, Al, Si or Li can be cited. Specifically, titanate spinel, tantalum oxides, niobium oxides and lithium niobate compounds can be cited, for example, Li 4 Ti 5 O 12 , Li 2 Ti2 O 5 、LiTaO 3 、LiNbO 3 、LiAlO 2 , Li 2 ZrO 3 , Li 2 WO 4 , Li 2 TiO 3 , Li 2 B 4 O 7 , Li 3 PO 4 , Li 2 MoO 4 , Li 3 BO 3 、LiBO 2 , Li 2 CO 3 , Li 2 SiO 3 、SiO 2 、TiO 2 、ZrO 2 、Al 2 O 3 and B 2 O 3 .
[0531] Furthermore, the surface of the electrode including the negative electrode active material may be surface-treated with sulfur or phosphorus.
[0532] Furthermore, the surface of the particles of the negative electrode active material may be subjected to a surface treatment using active light or active gas (for example, plasma) before or after the surface is coated.
[0533] (Positive electrode active material)
[0534] The positive electrode active material is preferably a material that can reversibly insert and / or release lithium ions. The positive electrode active material is not particularly limited, but is preferably a transition metal oxide, and more preferably contains a transition metal element M a (one or more elements selected from Co, Ni, Fe, Mn, Cu and V) transition metal oxide. In addition, the element M may be mixed in the transition metal oxide. b (Metals other than lithium, such as elements of Group 1 (Ia) and Group 2 (IIa) in the periodic table, Al, Ga, In, Ge, Sn, Pb, Sb, Bi, Si, P, and B.) As the mixing amount, it is preferably 2.5 to 3.5 relative to the transition metal element M. a The amount of Li / M is preferably 0 to 30 mol%. aA product synthesized by mixing so that the molar ratio of is 0.3 to 2.2.
[0535] Specific examples of transition metal oxides include (MA) transition metal oxides having a layered rock salt structure, (MB) transition metal oxides having a spinel structure, (MC) transition metal phosphate compounds containing lithium, (MD) transition metal halophosphate compounds containing lithium, and (ME) transition metal silicate compounds containing lithium. Among them, (MA) transition metal oxides having a layered rock salt structure are preferred, and LiCoO is more preferred. 2 or LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O 2 .
[0536] Examples of the transition metal oxide (MA) having a layered rock salt structure include LiCoO 2 (lithium cobalt oxide [LCO]), LiNi 2 O 2 (Lithium Nickel Oxide), LiNi 0.85 Co 0.10 Al 0.05 O 2 (lithium nickel cobalt aluminum oxide [NCA]), LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O 2 (NMC) and LiNi 0.5 Mn 0.5 O 2 (lithium manganese nickel oxide).
[0537] Examples of the transition metal oxide (MB) having a spinel structure include LiMn 2 O 4 (LMO), LiCoMnO 4 , Li 2 FeMn 3 O 8 , Li 2 CuMn 3 O 8 , Li 2 CrMn 3 O 8 and LiNi 0.5 Mn 1.5 O 4 (LNMO).
[0538] Examples of the lithium-containing transition metal phosphate compound (MC) include LiFePO 4 Li 3 Fe2 (PO 4 ) 3 Olivine type iron phosphate, LiFeP 2 O 7 Iron pyrophosphate, LiCoPO 4 Cobalt phosphates and Li 3 V 2 (PO 4 ) 3 (lithium vanadium phosphate) and other monoclinic NASICON-type vanadium phosphate salts.
[0539] Examples of the lithium-containing transition metal halophosphate compound (MD) include Li 2 FePO 4 F and other fluoroferric phosphates, Li 2 MnPO 4 F and other manganese fluorophosphates and Li 2 CoPO 4 F and other cobalt fluorophosphates.
[0540] Examples of the (ME) lithium-containing transition metal silicate compound include Li 2 FeSiO 4 , Li 2 MnSiO 4 Li 2 CoSiO 4 .
[0541] The shape of the positive electrode active material is not particularly limited, but preferably particulate. The volume average particle size of the positive electrode active material is not particularly limited, but preferably 0.1 to 50 μm. The volume average particle size of the positive electrode active material particles can be measured in the same manner as the volume average particle size of the negative electrode active material described above.
[0542] The positive electrode active material obtained by the calcination method can be used after being washed with water, an acidic aqueous solution, an alkaline aqueous solution, or an organic solvent.
[0543] The positive electrode active material may be surface-coated with the above-mentioned surface coating agent, sulfur or phosphorus, and also with active light in the same manner as the negative electrode active material.
[0544] The positive electrode active material may be used alone or in combination of two or more.
[0545] The electrode-forming composition may contain other components in addition to the lithium-based solid electrolyte and the active material.
[0546] The electrode-forming composition may contain a conductive auxiliary agent.
[0547] As the conductive auxiliary agent, a substance generally known as a conductive auxiliary agent can be used. As the conductive auxiliary agent, for example, graphites such as natural graphite and artificial graphite, carbon blacks such as acetylene black, Ketjen black and furnace black, amorphous carbon such as needle coke, fibrous carbon such as vapor-grown carbon fiber and carbon nanotubes, and carbonaceous materials such as graphene and fullerene can be cited as electron conductive materials. In addition, conductive polymers such as polyaniline, polypyrrole, polythiophene, polyacetylene and polyphenylene derivatives can be used.
[0548] In addition to the above-mentioned conductive additives, a common conductive additive containing no carbon atom, such as metal powder or metal fiber, may be used.
[0549] In addition, a conductive aid is an aid that does not insert or release Li during battery charge and discharge and does not function as an active material. Therefore, among conductive aids, substances that function as active materials in the active material layer during battery charge and discharge are also classified as active materials rather than conductive aids. Whether or not a conductive aid functions as an active material during battery charge and discharge is not unique, but is determined by the combination with the active material.
[0550] Furthermore, other components include the above-mentioned binder and lithium salt.
[0551] The electrode forming composition may contain a dispersion medium.
[0552] Examples of the dispersion medium include water and various organic solvents.
[0553] As other components in addition to the above-mentioned components, the electrode forming composition may include ionic liquids, thickeners, cross-linking agents (cross-linking agents that carry out cross-linking reactions by free radical polymerization, condensation polymerization or ring-opening polymerization), polymerization initiators (polymerization initiators that generate acids or free radicals by heat or light, etc.), defoaming agents, leveling agents, dehydrating agents and antioxidants.
[0554] The method of forming an electrode (negative electrode active material layer and positive electrode active material layer) using the above-mentioned electrode forming composition is not particularly limited, but a method of forming an electrode by applying the electrode forming composition can be cited. In addition, the formed coating film can be subjected to pressure treatment as needed.
[0555] The coating method of the electrode-forming composition is not particularly limited, and examples thereof include spray coating, spin coating, dip coating, slit coating, spray coating, aerosol deposition, thermal spraying, and bar coating.
[0556] In addition, after applying the electrode-forming composition, the obtained coating film may be dried as needed. The drying temperature is not particularly limited, but as a lower limit, it is preferably 30°C or more, more preferably 60°C or more, and further preferably 80°C or more. As an upper limit of the drying temperature, it is preferably 300°C or less, and more preferably 250°C or less.
[0557] The method of pressurizing the coating film is not particularly limited, but a method using a known pressurizing device (for example, a hydraulic cylinder press) can be mentioned.
[0558] The pressure applied during the pressurization treatment is not particularly limited, but is preferably 5 to 1500 MPa, more preferably 300 to 600 MPa.
[0559] The time of the pressurization treatment is not particularly limited, but is preferably 1 minute to 6 hours, more preferably 1 to 20 minutes, from the viewpoint of productivity.
[0560] Furthermore, during the pressurization treatment, a heat treatment may be performed. The heating temperature during the heat treatment is not particularly limited, but is preferably 30 to 300° C., and the heating time is preferably 1 minute to 6 hours.
[0561] The atmosphere during pressurization is not particularly limited, and examples thereof include atmospheric air, dry air (dew point -20°C or lower), and an inert gas (for example, argon, helium, and nitrogen) atmosphere.
[0562] <Solid electrolyte sheet>
[0563] The lithium-based solid electrolyte of the present invention may be contained in a solid electrolyte sheet.
[0564] The above-mentioned solid electrolyte sheet is preferably used as a solid electrolyte sheet for an all-solid-state battery.
[0565] The solid electrolyte sheet can be formed by molding the lithium-based solid electrolyte of the present invention into a sheet. The molding method is not particularly limited, and for example, the sheet can be formed by pressure molding a dispersion containing the lithium-based solid electrolyte of the present invention.
[0566] <Electrode sheet for all-solid-state secondary batteries>
[0567] The lithium-based solid electrolyte of the present invention may be contained in an electrode sheet for an all-solid-state secondary battery. In particular, the lithium-based solid electrolyte of the present invention may be contained in an electrode sheet for an all-solid-state lithium-ion secondary battery.
[0568] Hereinafter, the electrode sheet for an all-solid-state lithium-ion secondary battery will be mainly described in detail.
[0569] The electrode sheet for an all-solid-state lithium ion secondary battery of the present invention is a sheet-shaped molded body capable of forming an electrode active material layer of an all-solid-state lithium ion secondary battery, and can be preferably used for an electrode or a laminate of an electrode and a solid electrolyte layer.
[0570] Regarding the electrode sheet for the all-solid-state lithium-ion secondary battery of the present invention (also referred to as "electrode sheet"), as long as it is an electrode sheet having an active material electrode layer (hereinafter, also referred to as "active material electrode layer") selected from a group including a negative electrode active material layer and a positive electrode active material layer, it can be a sheet in which the active material electrode layer is formed on a substrate (collector), or it can be a sheet without a substrate and formed by an active material electrode layer. Usually, the electrode sheet is a sheet having a collector and an active material electrode layer, but also includes a method having a collector, an active material electrode layer and a solid electrolyte layer in sequence, and a method having a collector, an active material electrode layer, a solid electrolyte layer and an active material electrode layer in sequence.
[0571] The electrode sheet of the present invention may have the above-mentioned other layers. The thickness of each layer constituting the electrode sheet of the present invention is the same as the thickness of each layer described in the all-solid lithium ion secondary battery described later.
[0572] In the sheet for an all-solid-state lithium-ion secondary battery of the present invention, at least one layer of the active material electrode layer contains the lithium-based solid electrolyte of the present invention.
[0573] The method for producing the electrode sheet for an all-solid-state lithium ion secondary battery of the present invention is not particularly limited, and it can be produced, for example, by using the electrode-forming composition of the present invention and forming an active material electrode layer.
[0574] For example, there is a method in which the electrode-forming composition is applied on the current collector (optionally with other layers interposed therebetween) to form a coating film, and the coating film is subjected to a pressure treatment.
[0575] Examples of the method for applying the electrode-forming composition and the method for subjecting the coating film to a pressure treatment include the methods described in the section on the electrode-forming composition.
[0576] <All-solid-state secondary battery>
[0577] The all-solid-state secondary battery of the present invention comprises a positive electrode active material layer, a negative electrode active material layer opposite to the positive electrode active material layer, and a solid electrolyte layer disposed between the positive electrode active material layer and the negative electrode active material layer. The positive electrode active material layer is preferably formed on the positive electrode collector and constitutes the positive electrode. The negative electrode active material layer is preferably formed on the negative electrode collector and constitutes the negative electrode.
[0578] At least one of the negative electrode active material layer, the positive electrode active material layer and the solid electrolyte layer preferably contains the lithium-based solid electrolyte of the present invention.
[0579] That is, the present invention also relates to an electrode for an all-solid-state secondary battery, which comprises an active material layer containing an active material and the lithium-based solid electrolyte of the present invention, and a current collector.
[0580] Hereinafter, the all-solid-state lithium-ion secondary battery of the present invention will be mainly described in detail.
[0581] The all-solid-state lithium-ion secondary battery of the present invention comprises a positive electrode active material layer, a negative electrode active material layer opposite to the positive electrode active material layer, and a solid electrolyte layer disposed between the positive electrode active material layer and the negative electrode active material layer. The positive electrode active material layer is preferably formed on the positive electrode collector and constitutes the positive electrode. The negative electrode active material layer is preferably formed on the negative electrode collector and constitutes the negative electrode.
[0582] At least one of the negative electrode active material layer, the positive electrode active material layer and the solid electrolyte layer contains the lithium-based solid electrolyte of the present invention.
[0583] The thickness of the negative electrode active material layer, the solid electrolyte layer and the positive electrode active material layer is not particularly limited. Considering the size of a typical all-solid lithium ion secondary battery, the thickness of each layer is preferably 10 to 1000 μm, more preferably 20 μm or more and less than 500 μm.
[0584] The thickness of at least one of the positive electrode active material layer and the negative electrode active material layer is more preferably 50 μm or more and less than 500 μm.
[0585] The positive electrode active material layer and the negative electrode active material layer may each include a current collector on the side opposite to the solid electrolyte layer.
[0586] The all-solid lithium ion secondary battery of the present invention can be used as an all-solid lithium ion secondary battery in the state of the above structure according to the purpose, but in order to make it into the form of a dry cell, it is preferably further sealed in an appropriate shell for use. The shell can be a metallic shell or a shell made of resin (plastic). As a metallic shell, for example, a shell made of aluminum alloy and a shell made of stainless steel can be cited. The metallic shell is preferably divided into a shell on the positive side and a shell on the negative side, and is electrically connected to the positive collector and the negative collector, respectively. Preferably, the shell on the positive side is joined and integrated with the shell on the negative side via a gasket for preventing short circuits.
[0587] Below, reference Fig.16 , an all-solid-state lithium-ion secondary battery according to a preferred embodiment of the present invention is described, but the present invention is not limited thereto.
[0588] Fig.161 is a cross-sectional view schematically showing an all-solid-state lithium-ion secondary battery according to a preferred embodiment of the present invention. When viewed from the negative electrode side, the all-solid-state lithium-ion secondary battery 10 according to the present embodiment has a negative electrode current collector 1, a negative electrode active material layer 2, a solid electrolyte layer 3, a positive electrode active material layer 4, and a positive electrode current collector 5 in this order.
[0589] At least one of the negative electrode active material layer 2 , the positive electrode active material layer 4 , and the solid electrolyte layer 3 contains the lithium-based solid electrolyte of the present invention.
[0590] Each layer is in contact with each other and is adjacent to each other. By adopting this structure, when charging, electrons (e - ) is supplied to the negative electrode side, so that lithium ions (Li + ) accumulates here. On the other hand, during discharge, the lithium ions (Li + ) returns to the positive electrode side, so that electrons are supplied to the working portion 6. In the example shown in the figure, a light bulb is used as a model at the working portion 6 and is lit by discharge.
[0591] The negative electrode active material layer 2 contains the above-mentioned negative electrode active material.
[0592] The positive electrode active material layer 4 contains the above-mentioned positive electrode active material.
[0593] The positive electrode current collector 5 and the negative electrode current collector 1 are preferably electron conductors.
[0594] As the material forming the positive electrode collector, aluminum, aluminum alloy, stainless steel, nickel and titanium can be cited, preferably aluminum or aluminum alloy. In addition, as the positive electrode collector, a positive electrode collector (forming a thin film) treated with carbon, nickel, titanium or silver on the surface of aluminum or stainless steel can also be cited.
[0595] As the material forming the negative electrode collector, aluminum, copper, copper alloy, stainless steel, nickel and titanium can be enumerated, preferably aluminum, copper, copper alloy or stainless steel. In addition, as the negative electrode collector, a negative electrode collector processed by carbon, nickel, titanium or silver on the surface of aluminum, copper, copper alloy or stainless steel can also be enumerated.
[0596] The current collector is usually in the form of a thin film sheet, but may be in other shapes.
[0597] The thickness of the current collector is not particularly limited, but is preferably 1 to 500 μm.
[0598] Furthermore, it is also preferable to generate irregularities on the surface of the current collector by surface treatment.
[0599] The method for producing the all-solid-state lithium ion secondary battery is not particularly limited, and known methods may be mentioned. Among them, a method using the electrode-forming composition and / or the solid electrolyte layer-forming dispersion is preferred.
[0600] For example, a positive electrode forming composition containing a positive electrode active material can be applied to a metal foil as a positive electrode collector to form a positive electrode active material layer, and then a solid electrolyte layer forming dispersion is applied to the positive electrode active material layer to form a solid electrolyte layer. In addition, a negative electrode forming composition containing a negative electrode active material is applied to the solid electrolyte layer to form a negative electrode active material layer, and a negative electrode collector (metal foil) is overlapped on the negative electrode active material layer, and then the obtained laminate is subjected to a pressurization treatment, thereby obtaining an all-solid-state lithium ion secondary battery having a structure in which a solid electrolyte layer is sandwiched between the positive electrode active material layer and the negative electrode active material layer. It can also be enclosed in a housing as a desired all-solid-state lithium ion secondary battery.
[0601] Furthermore, an all-solid-state lithium ion secondary battery can be manufactured by reversing the formation method of each layer, forming a negative electrode active material layer, a solid electrolyte layer, and a positive electrode active material layer on a negative electrode collector, and stacking a positive electrode collector.
[0602] Furthermore, as another method, a positive electrode active material layer, a solid electrolyte layer, and a negative electrode active material layer may be separately produced and stacked to produce an all-solid-state lithium ion secondary battery.
[0603] The all-solid-state lithium-ion secondary battery is preferably initialized after manufacture or before use. There is no particular limitation on initialization, and it can be performed, for example, by performing initial charge and discharge under an increased pressure, and then releasing the pressure until the pressure is the pressure normally used for the all-solid-state lithium-ion secondary battery.
[0604] <Applications of all-solid-state secondary batteries>
[0605] The all-solid-state secondary battery (especially all-solid-state lithium ion secondary battery) of the present invention can be applied to various purposes. The application mode is not particularly limited. For example, when it is carried on an electronic device, a notebook computer, a pen input computer, a mobile computer, an e-book reader, a mobile phone, a wireless telephone sub-machine, a pager, a handheld terminal, a portable fax machine, a portable copier, a portable printer, a stereo headset, a video movie, a liquid crystal television, a handheld cleaner, a portable CD player, a mini disc player, an electric shaver, a transceiver, an electronic notepad, a calculator, a memory card, a portable recorder, a radio and a backup power supply can be cited. As other consumer products, automobiles, electric vehicles, motors, lighting equipment, toys, game equipment, load regulators, clocks, flashlights, cameras and medical equipment (pacemakers, hearing aids and shoulder massagers, etc.) can be cited. In addition, it can be used for various military purposes and space purposes. And, it can also be combined with solar cells.
[0606] Example
[0607] Below, enumerate embodiment and comparative example, feature of the present invention is further specifically described.As long as the material, usage amount, ratio, processing content and processing step etc. shown in the following examples do not depart from the gist of the present invention, then can be changed appropriately.Therefore, the scope of the present invention should not be interpreted restrictively by the specific example shown below.
[0608] <Example 1>
[0609] A ball mill (P-7 manufactured by Fritsch) was used, with a pot of stabilized zirconium oxide (YSZ) (45 ml), grinding balls of stabilized zirconium oxide (YSZ) (average particle size: 5 mm, number: 50), rotation speed: 370 rpm (revolutions per minute), LBO powder (powdered Li 2 B 4 O 7 Li 2 B 4 O 7 (247) powder (manufactured by RARE METALLIC Co., Ltd.) was ball-milled to obtain a lithium compound. The particle size distribution of the obtained lithium compound was about several μm to 10 μm, and the median particle size (D50) was 1.5 μm.
[0610] Add Li salt, i.e. Li(FSO 2 ) 2N(LiFSI) 0.05 g was added, and ball milling was performed for 100 hours. The obtained powder was added to water so that the powder concentration became 42 mass %, and ultrasonic treatment was performed for 30 minutes.
[0611] Next, the obtained dispersion was transferred to a glass petri dish and dried at 120° C. for 2 hours in the atmosphere to obtain a thin film of a lithium-based solid electrolyte. Next, the obtained thin film was peeled off to obtain a powder. After the obtained powder was left to stand for a certain period of time in the atmosphere, the following evaluation was performed.
[0612] In addition, the lithium-based solid electrolyte obtained above was used and the chromatogram was measured by SPring-8 BL04B2 (accelerating voltage: 61.4 keV, wavelength: ) Total X-ray scattering measurements were performed. The sample was sealed in a 2 mmφ or 1 mmφ Kapton capillary and the experiment was performed. In addition, as described above, the obtained data was Fourier transformed to obtain a reduced two-body distribution function.
[0613] As a result of the analysis, it was confirmed that in the reduced two-body distribution function G(r) obtained from the total X-ray scattering measurement, when r is In the range of , the peak G(r) shows more than 1.0, and the peak is located at The first peak and the peak G(r) show more than 1.0, and the peak is located at The second peak of the and The absolute value of G(r) in the following range is Outside the region is less than 1.0.
[0614] Based on the above results, it can be confirmed that the lithium-based solid electrolyte obtained by adding LiFSI and dispersing it in water is amorphous. On the other hand, in the lithium-based solid electrolyte, the peaks attributed to the BO distance and the BB distance observed in the conventional lithium tetraborate crystals are maintained. The conventional lithium tetraborate crystals are BO 4 Tetrahedron and BO 3 The triangles exist in a 1:1 structure (diborate structure), and it is inferred that the structure is maintained in the lithium-based solid electrolyte.
[0615] Solid-state lithium electrolyte was prepared at 120 °C 7 The full width at half maximum (FWHM) of the peak whose chemical shift appears in the range of -100 to +100 ppm in the spectrum obtained during Li-NMR measurement is 200 ppm relative to the solid state of the lithium-based solid electrolyte obtained above at 20°C. 7The ratio of the full width at half maximum (FWHM 1) of the peak whose chemical shift appeared in the range of -100 to +100 ppm in the spectrum obtained in Li-NMR measurement {(FWHM 2 / FWHM 1)×100} was 33%.
[0616] Will be solid at 20℃ 7 When the waveform of the first peak appearing in the range of -100 to +100 ppm in the spectrum obtained during Li-NMR measurement is separated, a second peak having a chemical shift in the range of -3 to 3 ppm and a half-maximum width of less than 5 ppm is obtained, and the ratio of the area intensity of the second peak to the area intensity of the first peak is 4%.
[0617] The lithium-based solid electrolyte obtained above was used and infrared absorption spectrum was measured under the above conditions. In the infrared absorption spectrum obtained, the -1 The maximum absorption intensity in the wave number region is relatively large compared to that in the region of 800 to 1600 cm -1 The ratio of the maximum absorption intensity in the wavenumber region is 0.72.
[0618] In the Raman spectrum of the obtained lithium-based solid electrolyte, the -1 The coefficient of determination obtained by least squares linear regression analysis in the wavenumber region is 0.9974.
[0619] The mass reduction rate of the obtained lithium-based solid electrolyte when heated from 25° C. to 800° C. was measured using a TG-DTA apparatus under the conditions described below. The mass reduction rate obtained was 29.8%.
[0620] Regarding the analysis of each element in the obtained lithium-based solid electrolyte, lithium and boron were quantitatively analyzed by ICP-OES, and fluorine and sulfur were quantitatively analyzed by combustion ion chromatography (combustion IC). Regarding N, the analysis mass of sulfur was estimated in consideration of each atomic weight in the Li salt, and regarding O, the analysis mass of elements other than O was calculated as a difference from the total amount of powder. The results are shown in the table described below.
[0621] <Example 2>
[0622] A ball mill (P-7 manufactured by Fritsch Japan Co., Ltd.) was used with a pot: stabilized zirconia (YSZ) (45 ml), grinding balls: stabilized zirconia (YSZ) (average particle size: 5 mm, number: 50), rotation speed: 370 rpm, LBO powder (powdered Li 2 B 4 O 7Li 2 B 4 O 7 (247) powder (manufactured by RARE METALLIC Co., Ltd.) was ball-milled to obtain a lithium compound.
[0623] The obtained lithium compound was added to water at a powder concentration of 42 mass %, and ultrasonic treatment was performed for 30 minutes.
[0624] Next, Li(FSO 2 ) 2 N(LiFSI) 0.05 g was added and ultrasonic treatment was performed for 30 minutes.
[0625] Next, the obtained dispersion was transferred to a glass petri dish and dried at 120° C. for 2 hours in the atmosphere to obtain a thin film of a lithium-based solid electrolyte. Next, the obtained thin film was peeled off to obtain a powder. After the obtained powder was allowed to stand for a certain period of time in the atmosphere, various evaluations were performed in the same manner as in Example 1. The results are summarized in the table described below.
[0626] <Example 3>
[0627] A ball mill (P-7 manufactured by Fritsch Japan Co., Ltd.) was used with a pot made of stabilized zirconia (YSZ) (45 ml), grinding balls made of stabilized zirconia (YSZ) (average particle size: 5 mm, weight: 70 g), a rotation speed of 530 rpm, LBO powder (powdered Li 2 B 4 O 7 Li 2 B 4 O 7 (247) powder (manufactured by RARE METALLIC Co., Ltd.) was ball-milled to obtain a lithium compound. The obtained lithium compound was added to water at a powder concentration of 42 mass %, and ultrasonic treatment was performed for 60 minutes to obtain a dispersion 1.
[0628] Next, Li(FSO 2 ) 22.32 g of N(LiFSI) was added to water at a powder concentration of 87 mass %, and ultrasonic treatment was performed for 60 minutes, thereby obtaining Solution 2.
[0629] The obtained dispersion 1 and solution 2 were mixed and stirred for 60 minutes with a magnetic stirrer. Then, the obtained dispersion was vacuum dried at 40°C and 10Pa for 15 hours to obtain a powder (lithium-based solid electrolyte). After the obtained powder was allowed to stand for a certain period of time in the atmosphere, various evaluations were performed in the same manner as in Example 1 in the atmosphere. The results are summarized in the table described below.
[0630] <Example 4>
[0631] A ball mill (P-7 manufactured by Fritsch Japan Co., Ltd.) was used with a pot made of stabilized zirconia (YSZ) (45 ml), grinding balls made of stabilized zirconia (YSZ) (average particle size: 5 mm, weight: 70 g), a rotation speed of 530 rpm, LBO powder (powdered Li 2 B 4 O 7 Li 2 B 4 O 7 (247) powder (manufactured by RARE METALLIC Co., Ltd.) was ball-milled to obtain a lithium compound. The obtained lithium compound was added to water at a powder concentration of 42 mass %, and ultrasonic treatment was performed for 60 minutes to obtain a dispersion 3.
[0632] Next, Li(FSO 2 ) 2 3.25 g of N(LiFSI) was added to water at a powder concentration of 87 mass %, and ultrasonic treatment was performed for 60 minutes, thereby obtaining a solution 4 .
[0633] The obtained dispersion 3 and solution 4 were mixed and stirred for 60 minutes with a magnetic stirrer. Then, the obtained dispersion was vacuum dried at 40°C and 10Pa for 15 hours to obtain a powder (lithium-based solid electrolyte). After the obtained powder was allowed to stand for a certain period of time in the atmosphere, various evaluations were performed in the same manner as in Example 1 in the atmosphere. The results are summarized in the table described below.
[0634] <Example 5>
[0635] A ball mill (P-7 manufactured by Fritsch Japan Co., Ltd.) was used with a pot made of stabilized zirconia (YSZ) (45 ml), grinding balls made of stabilized zirconia (YSZ) (average particle size: 5 mm, weight: 70 g), a rotation speed of 530 rpm, LBO powder (powdered Li 2 B 4 O 7 Li 2 B 4 O 7 (247) powder (manufactured by RARE METALLIC Co., Ltd.) was ball-milled to obtain a lithium compound. The obtained lithium compound was added to water at a powder concentration of 42 mass %, and ultrasonic treatment was performed for 60 minutes to obtain a dispersion 5.
[0636] Next, Li(FSO 2 ) 2 4.65 g of N(LiFSI) was added to water at a powder concentration of 87 mass %, and ultrasonic treatment was performed for 60 minutes, thereby obtaining a solution 6.
[0637] The obtained dispersion 5 and solution 6 were mixed and stirred for 60 minutes with a magnetic stirrer. Next, the obtained dispersion was vacuum dried at 40°C and 10 Pa for 15 hours to obtain a powder (lithium-based solid electrolyte). After vacuum drying, the obtained powder was used immediately and various evaluations were performed in the same manner as in Example 1 under the atmosphere. The results are summarized in the table described below.
[0638] <Example 6>
[0639] A ball mill (P-7 manufactured by Fritsch Japan Co., Ltd.) was used with a pot made of stabilized zirconia (YSZ) (45 ml), grinding balls made of stabilized zirconia (YSZ) (average particle size: 5 mm, weight: 70 g), a rotation speed of 530 rpm, LBO powder (powdered Li 2 B 4 O 7 Li 2 B 4 O 7(247) powder (manufactured by RARE METALLIC Co., Ltd.) was ball-milled to obtain a lithium compound. The obtained lithium compound was added to water at a powder concentration of 42 mass %, and ultrasonic treatment was performed for 60 minutes to obtain a dispersion 7.
[0640] Next, Li(F 3 CSO 2 ) 2 7.13 g of N(LiTFSI) was added to water at a powder concentration of 87% by mass, and ultrasonic treatment was performed for 60 minutes, thereby obtaining a solution 8.
[0641] The obtained dispersion 7 and solution 8 were mixed and stirred for 60 minutes with a magnetic stirrer. Then, the obtained dispersion was vacuum dried at 40°C and 10Pa for 15 hours to obtain a powder (lithium-based solid electrolyte). After the obtained powder was allowed to stand for a certain period of time in the atmosphere, various evaluations were performed in the same manner as in Example 1 in the atmosphere. The results are summarized in the table described below.
[0642] In Example 6, the carbon content shown in Table 1 described later was estimated from the analyzed mass of sulfur in consideration of the atomic weights of each atom in the Li salt.
[0643] <Comparative Example 1>
[0644] The powdered Li 2 B 4 O 7 The crystal (LBO powder) (manufactured by RARE METALLIC Co., Ltd.) (crystal powder) was compacted at 27° C. (room temperature) at an effective pressure of 200 MPa to obtain a comparative green compact. The ion conductivity of the obtained green compact could not be detected.
[0645] <Reference Example 1>
[0646] A ball mill (P-7 manufactured by Fritsch Japan Co., Ltd.) was used with a pot: stabilized zirconia (YSZ) (45 ml), grinding balls: stabilized zirconia (YSZ) (average particle size: 5 mm, number: 50), rotation speed: 500 rpm, LBO powder (powdered Li 2 B 4 O 7 Li 2 B 4 O 7The (LBO) powder (manufactured by RARE METALLIC Co., Ltd.) was ball-milled to obtain a lithium compound. The obtained lithium compound was left to stand for a certain period of time in the atmosphere, and then various evaluations were carried out in the same manner as in Example 1.
[0647] The particle size distribution of the obtained lithium compound was about several μm to 10 μm, and the median particle size (D50) was 1.5 μm. The bulk elastic modulus of the obtained lithium compound was 36 GPa. The bulk elastic modulus of the LBO powder before ball milling was 47 GPa.
[0648] The measurement of the bulk modulus of lithium compounds is implemented by ultrasonic attenuation method. Specifically, first, a suspension obtained by suspending lithium compounds in pure water is prepared. The content of lithium compounds in the suspension is set to 1.2% by mass relative to the total mass of the suspension. Then, the ultrasonic attenuation spectrum of the above-mentioned suspension is measured, and the bulk modulus (GPa) of the lithium compound is obtained based on the fitting based on the scattering attenuation theory formula. In addition, when calculating the bulk modulus, the density of a specific solid electrolyte is set to 2.3g / mL, and the Poisson's ratio is set to 0.12 and fitted. And, about the fitting based on the above-mentioned scattering attenuation theory formula, the bulk modulus is calculated using the formula (7), formula (12) and formula (13) recorded in Kohjiro Kubo et al., (et al.) Ultrasonics (ultrasonics) 62 (2015) 186-194 pages.
[0649] <Various Reviews>
[0650] (Ionic conductivity measurement (1))
[0651] The lithium-based solid electrolyte obtained in each example was pressed at 27°C (room temperature) with an effective pressure of 200 MPa to obtain a powder compact. In foil was set on the surface and back of the obtained powder compact, and the ion conductivity was estimated from the analysis of the arc diameter of the Cole-Cole diagram (Nyquist diagram) obtained from the AC impedance measurement via two In electrodes (measurement temperature 27°C or 60°C, applied voltage 50mV, measurement frequency range 1Hz~1MHz). The values of ion conductivity obtained at measurement temperatures of 27°C and 60°C are shown in Table 2 described later.
[0652] 〔Water content〕
[0653] The content of water contained in the lithium-based solid electrolyte obtained in each example was determined based on the measurement results of the lithium-based solid electrolyte by an elemental analysis method and the types of components used.
[0654] Regarding the lithium-based solid electrolytes obtained in Examples 1 to 6, the water contents relative to the total mass of the lithium-based solid electrolytes determined by the above method are summarized in Table 2 described below.
[0655] (SEM-EDX analysis)
[0656] 400 mg of the lithium solid electrolyte obtained in Example 5 was pressed and molded using a press molding machine at an effective pressure of 200 MPa at 27°C to produce a powder compact (granules) (10 mmφ, 2 mm thickness). The obtained powder compact was clamped with a battery clamp and dried by storing it in an airtight container containing a silica desiccant for 48 hours under a restraining pressure of 60 MPa.
[0657] The dried powder compact was cut, and the exposed rough cross section was polished using a cross section polisher (CCP) device under the following conditions.
[0658] Device: "SM-9020CP" manufactured by JEOL Ltd.
[0659] Processing time: 4.5 hours
[0660] Processing temperature: -120℃
[0661] Processing range: 500μm (half width)
[0662] Next, a K-ray spectrum of each of sulfur, boron, nitrogen, oxygen, and fluorine was detected using the following SEM-EDX apparatus, thereby obtaining a mapping image showing the composition distribution on the exposed cross section.
[0663] Field emission electron probe microanalyzer (FE-EPMA): JEOL Ltd. "JXA-8530F"
[0664] Accelerating voltage: 10kV
[0665] Observation magnification: 100 to 1000 times
[0666] Based on the mapping images obtained by the above-mentioned device, the cross-sectional structure of the powder compact was observed and the components were analyzed.
[0667] exist Fig.14, a mapping image obtained by the above-mentioned SEM-EDX analysis is shown. In the obtained mapping image, the area where the sulfur element is detected by the SEM-EDX analysis is represented by the bright part, and a mesh structure is formed in which the dark part in the form of particles is surrounded by the bright part forming the continuous phase. In the lithium-based solid electrolyte obtained in Example 5, the sulfur element is contained in the lithium salt but not in lithium tetraborate and water. Therefore, the results of the SEM-EDX analysis and observation confirmed that on the cross-section of the molded body obtained by pressurizing the lithium-based solid electrolyte obtained in Example 5, a mesh structure is formed by the area where the lithium salt exists. As shown Fig.14 As shown, the lithium salt is contained and functions as an excellent ion conduction path having a wide mesh structure, thereby presumably obtaining excellent ion conductivity.
[0668] In the same manner as in Example 5, a powder compact was prepared using the lithium-based solid electrolytes obtained in Examples 1 to 4 and 6, and SEM-EDX analysis was performed on the cross section of the obtained powder compact. It was confirmed that a network structure was formed by the region where the lithium salt existed.
[0669] (TG-DTA)
[0670] The lithium-based solid electrolyte obtained in Example 5 was pressed and molded using a press molding machine at an effective pressure of 200 MPa at 27°C to produce a powder compact (granules) (10 mm φ, 1 mm thick). The obtained powder compact was clamped in a battery fixture and freeze-dried in a vacuum for 18 hours under a restraining pressure of 60 MPa. The freeze-dried powder compact was crushed, and 20 mg of the obtained powder was subjected to thermogravimetric differential thermal analysis (TG-DTA) under the following conditions.
[0671] · Apparatus: "TG-DTA 2000S" manufactured by Makc Science Co., Ltd.
[0672] Temperature program: 25℃ (room temperature) - 800℃ (slope: 10℃ / min)
[0673] ·Measurement atmosphere: atmospheric
[0674] Sample weight: 20 mg
[0675] Measuring container: Pt deep dish
[0676] exist Fig.17In the figure, a graph obtained by the above-mentioned TG-DTA measurement is shown. In the obtained graph, a combustion peak is shown near a temperature of 149°C. It is speculated that the combustion peak originates from the combustion of the Li salt (LiFSI). In the case of using LiFSI alone to carry out TG-DTA measurement under the above-mentioned measurement conditions, since the combustion peak of LiFSI is shown near 120°C, it is speculated that in the pressed powder of the lithium-based solid electrolyte of Example 5, the Li salt and BM-LBO247 (ball-milled Li 2 B 4 O 7 ) and / or water, the combustion peak may shift to a higher temperature.
[0677] (TG-MS)
[0678] According to the method described in the above (TG-DTA), the powder compact of the lithium solid electrolyte obtained in Example 5 was prepared, and the obtained powder compact was freeze-dried. The freeze-dried powder compact was pulverized, and the obtained powder was subjected to thermogravimetric mass spectrometry (TG-MS) under the following conditions.
[0679] Device: "STA2500" manufactured by NETCH Co., Ltd. and "JMS-Q1050GC" manufactured by JEOL Ltd.
[0680] Temperature program: 40℃-500℃ (slope: 5℃ / min)
[0681] ·Measurement atmosphere: He
[0682] Sample weight: 84.46 mg
[0683] ·Measurement container: Al deep plate
[0684] Mass spectrometer: Quadrupole mass spectrometer (QMS)
[0685] Ionization device: EI 70eV capillary (empty tube with inner diameter 0.32mm)
[0686] Scanning range: 10-1000Da
[0687] Transmission line temperature: 300°C
[0688] exist Fig.18, a graph obtained by the above-mentioned TG-MS measurement is shown. In the obtained graph, a weight loss is observed between 100 and 137°C, during which components with a molecular weight of 18 are mainly detected. In this way, a component with a molecular weight of 18, which is presumed to be water, is detected in the temperature range exceeding 100°C, thereby suggesting the presence of water (especially water in the third and fourth states) in the compressed powder of the lithium-based solid electrolyte obtained in Example 5. In addition, a sharp weight loss is observed from 137°C. At this temperature, components presumed to be derived from the combustion of the Li salt (LiFSI) are mainly detected, but components with a molecular weight of 18 are also detected. Therefore, it is presumed that water constrained by the Li salt is likely to evaporate with the combustion of the Li salt.
[0689] The results of the TG-MS measurements suggest that, in the lithium-based solid electrolyte of the present invention, water (especially water in the third and fourth states) may be confined to the region where the Li salt exists.
[0690] ( 1 H-NMR)
[0691] The powder of the lithium solid electrolyte obtained in Example 5 was placed in a closed test tube under a nitrogen atmosphere and subjected to the above conditions. 1 H-NMR measurement.
[0692] exist Fig.11 In the figure, it is shown that the above 1 The spectrum obtained by H-NMR measurement. A sharp peak and a broad peak were observed from the obtained spectrum. Therefore, it is inferred that in the lithium-based solid electrolyte of Example 5, there are hydrogen atoms with high relative mobility corresponding to the sharp peak and hydrogen atoms with low relative mobility corresponding to the broad peak.
[0693] ( 19 F-NMR)
[0694] The powder of the lithium solid electrolyte obtained in Example 5 was placed in a closed test tube under a nitrogen atmosphere and solidified under the above conditions. 19 F-NMR measurement.
[0695] exist Fig.19 In the figure, it is shown that the above 19 Spectrum obtained by F-NMR measurement. The above measurement results presume that a sharp peak appears in the chemical shift range of -200 to +300 ppm, indicating the presence of a lithium salt or anion that has high relative mobility and contributes to ion conductivity.
[0696] (Total X-ray Scattering Measurement)
[0697] The lithium-based solid electrolytes of the examples, the crystal powders of the comparative examples, and the lithium compounds of the reference examples were used and the results were analyzed by SPring-8 BL04B2 (accelerating voltage: 61.4 keV, wavelength: ) Total X-ray scattering measurements were performed. The sample was sealed in a 2 mmφ or 1 mmφ Kapton capillary and the experiment was performed. In addition, as described above, the obtained data was Fourier transformed to obtain a reduced two-body distribution function.
[0698] The results of the analysis show that in the reduced two-body distribution function G(r) obtained from the total X-ray scattering measurement, there is a peak located at r The first peak and the peak top in the range of r are In the case where the peak G(r) of the first peak and the peak G(r) of the second peak show a value greater than 1.0, the "Short-range G(r)" column in Table 2 is set to "A", and all other cases are set to "B".
[0699] In Examples 1 to 6 shown in Table 2 described later and Examples 9 to 13 shown in Table 6 described later, the peak top G(r) value of the first peak was 1.2 or more.
[0700] Furthermore, in the above-mentioned reduced two-body distribution function G(r), when r is greater than and When the absolute value of G(r) in the following range is less than 1.0, the "Long-range G(r)" column in Table 2 is designated as "A", and the other cases are designated as "B".
[0701] (X-ray diffraction measurement)
[0702] The lithium-based solid electrolyte of the example, the crystal powder of the comparative example, and the lithium compound of the reference example were measured by X-ray diffraction using CuKα radiation at 0.01° / step and 3° / minute.
[0703] The measurement result is set to "A" when the above-mentioned requirement Y is satisfied in the obtained diffraction pattern, and is set to "B" when the above-mentioned requirement Y is not satisfied.
[0704] In addition, in Examples 1 to 6 shown in Table 2 described later and Examples 7 to 13 shown in Table 6 described later, in the X-ray diffraction pattern, the first peak, the second peak, the third peak and the fourth peak do not exist, or at least one intensity ratio of specific peaks selected from the group including the first peak, the second peak, the third peak and the fourth peak is less than 2.0.
[0705] In Table 1, in the "Element Analysis" column, the composition of the lithium-based solid electrolyte obtained in each example determined by the above-mentioned element analysis method is expressed as the molar content of each element as a relative value when the B content is set to "4.00".
[0706] In the table, the column "Water (%)" shows the content of water contained in the lithium-based solid electrolyte obtained in each example (unit: mass %).
[0707] In the table, the column "Ratio of half-peak full width (%)" indicates that the solid state of the lithium-based solid electrolyte was carried out at 120°C. 7 The full width at half maximum of the peak whose chemical shift appears in the range of -100 to +100 ppm in the spectrum obtained during Li-NMR measurement is 200 ppm higher than that of the solid state electrolyte at 20°C. 7 The ratio (%) of the half-maximum full width of a peak in which a chemical shift appears in the range of -100 to +100 ppm in a spectrum obtained during Li-NMR measurement.
[0708] In the table, the "area intensity ratio" column indicates the ratio of the area intensity of the second peak to the area intensity of the first peak. The "value (%)" column indicates a specific value, and the "range" column indicates the range to which the value of each embodiment and comparative example belongs according to the following criterion (area intensity ratio range). In Examples 3, 5, and 6, the "value (%)" column does not indicate a value, and the "range" column indicates the range to which the value belongs.
[0709] (Area intensity ratio range)
[0710] A: When the area strength ratio is 15% or more
[0711] B: When the ratio of area strength is 0.5% or more and less than 15%
[0712] C: When the ratio of area intensity is less than 0.5%
[0713] In the table, the column “Maximum Absorption Intensity Ratio” indicates the maximum absorption intensity ratio in the infrared absorption spectrum of lithium-based solid electrolytes in the range of 3000 to 3500 cm -1 The maximum absorption intensity in the wave number region is relatively large compared to that in the region of 800 to 1600 cm -1 The "Value" column indicates a specific value, and the "Range" column indicates to which range the value of each embodiment and comparative example belongs according to the following standard (maximum absorption intensity ratio range). In addition, in Examples 3, 5, and 6, the "Value" column does not indicate a value, and the "Range" column indicates to which range the value belongs.
[0714] (Maximum absorption intensity ratio range)
[0715] A: When the maximum absorption intensity ratio is 0.20 or more
[0716] B: When the maximum absorption intensity ratio is less than 0.20
[0717] In the table, "Maximum absorption intensity ratio (at N 2 The "(under atmosphere and heated at 90°C)" column indicates that the obtained lithium-based solid electrolyte was heated at 90°C for 5 minutes, and then the infrared absorption spectrum of the lithium-based solid electrolyte after the heat treatment was measured. In the obtained infrared absorption spectrum, the infrared absorption spectrum of the obtained lithium-based solid electrolyte in the range of 3000 to 3500 cm -1 The maximum absorption intensity in the wave number region is relatively large compared to that in the region of 800 to 1600 cm -1 The ratio of the maximum absorption intensity in the wave number region.
[0718] In the table, the column “Determination coefficient” shows that for Examples 1 and 2, the Raman spectra of 600 to 850 cm -1 The coefficient of determination was obtained by linear regression analysis using the least squares method within the wavenumber region.
[0719] In the table, in the column "Requirement T", the case where the requirement T is satisfied is set as "A", and the case where the requirement T is not satisfied is set as "B". In addition, in the Raman spectra of the lithium-based solid electrolytes of Examples 1 to 6, the Raman spectra of 710 to 730 cm specified in requirement T are -1 The peak has a full width at half maximum of 5 cm -1 The first peak above is at 770-790cm -1 The peak has a full width at half maximum of 5 cm -1 The second peak above 1020-1040cm -1 The peak has a full width at half maximum of 5 cm -1 The third peak mentioned above does not exist.
[0720] In the table, the column "Mass reduction rate (%)" indicates the mass reduction rate when the above-mentioned lithium-based solid electrolyte is heated to 800°C.
[0721] In the table, “-” means that the measured values are not shown.
[0722] In Examples 1 to 6, Li 2 B 4 O 7 The lithium compounds obtained by ball milling the (247) powder (manufactured by RARE METALLIC Co., Ltd.) all satisfy any one of the above-mentioned requirements α, β, γ and δ.
[0723] More specifically, in Examples 1 to 6, Li 2 B 4 O 7 In the Raman spectrum of a lithium compound obtained by ball-milling a (247) powder (manufactured by RARE METALLIC Co., Ltd.), none of the first to third peaks specified in the requirement δ exists.
[0724] Furthermore, in Examples 1 to 6, Li 2 B 4 O 7 (247) In the X-ray diffraction pattern of a lithium compound obtained by ball milling a powder (manufactured by RARE METALLIC Co., Ltd.) obtained from X-ray diffraction measurement using CuKα rays, none of the first peak to the fourth peak specified in requirement α is present, or at least one specific peak selected from the group consisting of the first peak, the second peak, the third peak and the fourth peak is present, and the intensity ratio calculated by the intensity measurement method of at least one of the specific peaks is less than 2.0.
[0725] [Table 1]
[0726]
[0727]
[0728] As shown in the above table, the lithium-based solid electrolyte of the present invention exhibits the desired effect. In particular, in the invention described in Patent Document 1, the ion conductivity is 10 -5 S cm -1 It was confirmed that the ion conductivity of the present invention was relatively superior.
[0729] As shown in Table 1, in Examples 3 to 6, it was confirmed that the content of Li was higher. As the reason for the increase in the content of Li, in Examples 3 to 6, a method of mixing an aqueous solution containing a mechanically milled lithium compound and an aqueous solution containing a lithium salt (method 3 in the above-mentioned step 2B) was implemented, and according to this method, the content of Li (FSO 2 ) 2 The mixing amount of N(LiFSI) is increased, so it is speculated that the amount of Li entering the lithium-based solid electrolyte has increased. In addition, it is confirmed that the ion conductivity is further improved in Examples 3 to 6 as shown in Table 2. It is speculated that the reason for the improvement in ion conductivity is that the Li composition ratio (content ratio) is increasing, and the increased Li includes Li with high mobility, thereby increasing Li with high mobility as a whole.
[0730] Furthermore, as shown in the "Maximum Absorption Intensity Ratio" column and the "Maximum Absorption Intensity Ratio (at N2 As shown in the column "(heated at 90°C in an atmosphere)", in Example 4, the heat treatment reduced the -1 The maximum absorption intensity in the wave number region is relatively large compared to that in the region of 800 to 1600 cm -1 This is presumably because water (mainly water in the first state) contained in the lithium-based solid electrolyte evaporates.
[0731] In the reduced two-body distribution function G(r) obtained from the total X-ray scattering measurement of the crystal powder of Comparative Example 1, there is a peak located at The first peak (corresponding to the vicinity of BO) and the peak are located at The second peak of the BB (corresponding to the BB), the peak G (r) of the first peak and the second peak is greater than 1.0 (reference Fig. 20 ). And, in addition, there is a peak located at and The peak values of each peak value G(r) are greater than 1.0 (reference Fig. 20 ).
[0732] In contrast, in the reduced two-body distribution function G(r) obtained from the total X-ray scattering measurement of the lithium compound of Reference Example 1, there is a peak located at The first peak (corresponding to the vicinity of BO) and the peak are located at The second peak (corresponding to the vicinity of BB) has a peak G(r) of more than 1.0 at the first and second peaks. and The absolute value of G(r) in the following range is less than 1.0.
[0733] These results confirm that the mechanical polishing process can increase the r to more than and On the other hand, after the mechanical grinding treatment, the peaks attributed to the distance between BO and the distance between BB observed in the ordinary lithium tetraborate crystals were also maintained. Based on this result, it is believed that in the mechanical grinding treatment, the BO contained in the ordinary lithium tetraborate crystals 4 Tetrahedron and BO 3 The structure in which the triangle exists in a 1:1 ratio (diborate structure) is maintained.
[0734] exist Fig.21 , the X-ray diffraction pattern of the crystal powder of Comparative Example 1 is shown. Fig.21As shown, in Comparative Example 1, when the above-mentioned requirement Y is not satisfied, multiple peaks with small widths are observed. More specifically, the strongest peak corresponding to the (1,1,2) surface is observed at a position where the 2θ value is 21.78°. As other major diffraction peaks, a peak corresponding to the (2,0,2) surface is shown at a position of 25.54°, a peak corresponding to the (2,1,3) surface is shown at a position of 33.58°, and a peak corresponding to the (3,1,2) surface is shown at a position of 34.62°, and the intensities of these three peaks are roughly the same. These peaks originate from the crystal components.
[0735] In contrast, Fig. 22 , the X-ray diffraction pattern of the lithium-based solid electrolyte of Example 4 is shown. Fig. 22 As shown, in Example 4, even if the intensity ratio 5.0 specified in the above-mentioned requirement Y is set to 2.0, the requirement is satisfied. Fig.21 It can be seen that the existing crystalline components are amorphized by the mechanical grinding process, and the sharp peak derived from the lithium tetraborate crystal disappears and becomes broad.
[0736] (Ionic conductivity measurement (2))
[0737] The powder compact (pellets) (10 mmφ, 0.9 mm thick) of the lithium-based solid electrolyte obtained in Example 4 was vacuum dried at 27° C. under 60 MPa constraint, and the pressure change with vacuum drying time and the ion conductivity were evaluated.
[0738] The production method of the powder compact and the evaluation of ion conductivity were carried out in the same manner except that the In electrode described in the above (Ion conductivity measurement (1)) was replaced with a Ti electrode.
[0739] [Table 3]
[0740]
[0741] The lithium solid electrolyte of Example 4 has a wavelength of 3000-3500 cm in the infrared absorption spectrum. -1 The OH stretching peak of is increased, so it is considered that a large amount of OH groups or water exists. In addition, as mentioned above, it is also estimated that there are water in the first state to the fourth state.
[0742] In the above evaluation, it was confirmed that in addition to the water in the first state and the second state, there were also substances with good ion conductivity. Therefore, the particles were first dried under conditions where it was believed that the water in the first state was mainly evaporated, and then the particles were further dried under conditions with increased strength, thereby evaluating the ion conductivity of each stage.
[0743] As shown in Table 3, when the drying time was 5 minutes and the pressure was 200 Pa, it was considered that the water in the first state was mainly in the state of evaporation, but the ion conductivity showed 3.8×10 -3 Next, it can be seen that after vacuum drying under the conditions of drying time of 1080 minutes and pressure of 15 Pa, even in the case where water in the first state and the second state is considered to have evaporated, the ion conductivity shows 5.7×10 -4 S / cm, it was confirmed that there is a substance with good ion conductivity in addition to the water in the first and second states. Although it is not clear, it is estimated to be water (especially the water in the third and fourth states).
[0744] Furthermore, although the phenomenon occurring during the drying process is not yet clear, as shown in Table 3, when the drying time was 50 minutes and the pressure was 10 Pa, it is speculated that under these conditions, water (especially water in the 3rd and 4th states) remained and the water was gradually desorbed. In addition, when the drying time was 1080 minutes and the pressure was 15 Pa, it is speculated that water having a property that is more difficult to evaporate (especially water in the 4th state) remained.
[0745] The above results suggest that water with good ion conductivity (particularly water in the third and fourth states) exists in the lithium-based solid electrolyte from the viewpoint of exhibiting excellent ion conductivity even after a prolonged drying time.
[0746] Furthermore, the temperature was raised to 100°C while the pressure was maintained and the drying was performed. The ion conductivity was measured and the result showed that the ion conductivity was 1.2×10 ―5 In this way, even when it is presumed that only water in the fourth state exists in the lithium-based solid electrolyte, ion conductivity is exhibited.
[0747] (Ionic conductivity measurement (3))
[0748] The lithium-based solid electrolyte obtained in Example 5 was pressed and molded using a press molding machine at an effective pressure of 200 MPa at 27°C to produce a powder compact (granules) (10 mm φ, thickness 0.8 mm). The obtained powder compact was clamped with a battery fixture and vacuum dried for 15 hours at a temperature of 40°C and a pressure of 20 Pa under a restraining pressure of 60 MPa. The ion conductivity was then measured under the temperature conditions shown in the following table. In the measurement of the ion conductivity of the powder compact, the In electrode was replaced with the Al electrode of the above-mentioned battery fixture. Otherwise, the method described in the above-mentioned (Ion conductivity measurement (1)) was followed.
[0749] The obtained values of ion conductivity at each temperature are shown in Table 4 described later.
[0750] [Table 4]
[0751]
[0752] It is presumed that the following state is present: as shown in Table 4, at least the first state of water contained in the powder compact is frozen at a temperature below 0°C, and at a temperature of -10°C, the second state of water is also frozen. As a result, 6.7×10 -4 The ion conductivity of 1.3477 W / cm indicates that there is a substance with good ion conductivity other than water in the first and second states. Although it is not clear, it is estimated to be water (especially water in the third and fourth states).
[0753] The above results suggest that water with good ion conductivity (particularly water in the third and fourth states) exists in the lithium-based solid electrolyte from the viewpoint of showing excellent ion conductivity even under a temperature condition of -10°C.
[0754] (Karl Fischer measurement)
[0755] 200 mg of the powder of each lithium-based solid electrolyte obtained in Example 5 was pressurized using a uniaxial press (200 MPa, 2 minutes) to obtain a compressed powder. The obtained compressed powder was placed in a closed cell, and dried for 1 month under atmospheric pressure using silica sealed with the cell while applying a pressure of 60 MPa. The cell was opened under an argon atmosphere, and 5 to 10 mg of the dried sample was placed in a small medicine bottle for measurement, and the small medicine bottle was sealed. In addition, a small medicine bottle sealed in an environment where the above sample was collected and sealed as a blank was also prepared. The small medicine bottle was set in the moisture evaporation device of the Karl Fischer measuring device, and the moisture was evaporated by heating from room temperature (27°C) to 300°C. Then, the water content evaporated by Karl Fischer titration was measured using a coulometric moisture measuring device.
[0756] The results of the above measurements show that the amount of water B evaporated from the lithium-based solid electrolyte during heating from room temperature to 200°C is greater than the amount of water A evaporated from the lithium-based solid electrolyte during heating from room temperature to 100°C, suggesting that there is water in the lithium-based solid electrolyte that is more strongly bound by the surroundings than the water in the first state.
[0757] <Example 7>
[0758] A ball mill (P-7 manufactured by Fritsch Japan Co., Ltd.) was used with a pot made of stabilized zirconia (YSZ) (45 ml), grinding balls made of stabilized zirconia (YSZ) (average particle size: 5 mm, weight: 70 g), a rotation speed of 530 rpm, LBO powder (powdered Li 2 B 4 O 7 Li 2 B 4 O 7 (247) powder (manufactured by RARE METALLIC Co., Ltd.) was ball-milled to obtain a lithium compound. The obtained lithium compound was added to water at a powder concentration of 42 mass %, and ultrasonic treatment was performed for 60 minutes to obtain a dispersion 9.
[0759] Next, Li(F 3 CSO 2 ) 2 7.12 g of N(LiTFSI) was added to water at a powder concentration of 87% by mass, and ultrasonic treatment was performed for 60 minutes, thereby obtaining a solution 10.
[0760] The obtained dispersion 9 and solution 10 were mixed and stirred for 60 minutes using a magnetic stirrer. Next, the obtained dispersion was vacuum dried at 40° C. and 10 Pa for 15 hours to obtain a powder of a lithium-based solid electrolyte. The obtained powder was allowed to stand for a certain period of time in the atmosphere, and then various evaluations were performed in the same manner as in Example 1.
[0761] <Example 8>
[0762] The water and Li(F) in the obtained lithium-based solid electrolyte 3 CSO 2 ) 2 Except that the content of N(LiTFSI) was changed to the amount described in the table below, a powder of a lithium-based solid electrolyte was obtained in the same manner as in Example 7. After the obtained powder was left to stand for a certain period of time in the atmosphere, various evaluations were performed in the same manner as in Example 1 in the atmosphere.
[0763] <Example 9 to Example 13>
[0764] Li(F 3 CSO 2 ) 2 N(LiTFSI) was changed to Li(FSO2 ) 2 N(LiFSI), and the water and Li(FSO 2 ) 2 The content of N(LiFSI) was changed to the amount described in the table described later, and except for this, a powder of a lithium-based solid electrolyte was obtained in the same manner as in Example 7. After the obtained powder was allowed to stand for a certain period of time in the atmosphere, various evaluations were performed in the atmosphere in the same manner as in Example 1. In addition, for the powder of the lithium-based solid electrolyte obtained in Example 13, various evaluations in the atmosphere were performed immediately after the above-mentioned vacuum drying treatment.
[0765] In Table 5, the columns "BM-LBO247", "Li salt" and "water" indicate the components in the powders obtained in each Example and Reference Example 1. Specifically, "BM-LBO247" indicates Li salt that has been ball-milled. 2 B 4 O 7 "Li salt" refers to the lithium salt (Li(F 3 CSO 2 ) 2 N(LiTFSI), Li(FSO 2 ) 2 N(LiFSI)). The "molar ratio" column in the table indicates the relative molar ratio of each component when the molar amount of BM-LBO247 is set to 1. For example, in the powder obtained in Example 7, the molar ratio of Li salt to BM-LBO247 is 1, and the molar ratio of water to BM-LBO247 is 12. In addition, the "mass ratio" column in the table indicates the relative mass ratio of each component when the total mass of BM-LBO247, Li salt and water is set to 100. For example, the mass ratio of BM-LBO247, Li salt and water contained in the powder obtained in Example 7 is 26:44:30.
[0766] The above-mentioned molar ratio and mass ratio were calculated by the following method.
[0767] Regarding the analysis of each element in the obtained powder, lithium and boron were quantitatively analyzed by ICP-OES, and fluorine and sulfur were quantitatively analyzed by combustion ion chromatography (combustion IC), and N was estimated from the analyzed mass of sulfur in consideration of each atomic weight in the Li salt, and O was calculated as the difference from the total amount of powder by adding the analyzed masses of elements other than O. In Examples 7 and 8, the carbon content was estimated from the analyzed mass of sulfur in consideration of each atomic weight in the Li salt.
[0768] The molar ratio of BM-LBO247 to Li salt in the powder was calculated based on the molar ratio of an element (e.g., B) existing only in BM-LBO247 to an element (e.g., a specific element) existing only in Li salt. Furthermore, the molar ratio of BM-LBO247 to water was calculated by subtracting the molar ratio of O contained in BM-LBO247 and Li salt from the molar ratio of O in the powder to calculate the molar amount of O derived from water, and the obtained molar amount of O derived from water and the molar amount of BM-LBO247 were used for calculation.
[0769] The mass ratio of each component was calculated based on the calculated molar amount and molecular weight of each component.
[0770] In Examples 7 to 13, Li 2 B 4 O 7 The lithium compounds obtained by ball milling the (247) powder (manufactured by RARE METALLIC Co., Ltd.) all satisfy the above-mentioned requirements α, β, γ and δ.
[0771] More specifically, in Examples 7 to 13, Li 2 B 4 O 7 In the Raman spectrum of a lithium compound obtained by ball-milling a (247) powder (manufactured by RARE METALLIC Co., Ltd.), none of the first to third peaks specified in the requirement δ exists.
[0772] Furthermore, in Examples 7 to 13, Li 2 B 4 O 7 (247) In the X-ray diffraction pattern of a lithium compound obtained by ball milling a powder (manufactured by RARE METALLIC Co., Ltd.) obtained from X-ray diffraction measurement using CuKα rays, none of the first peak to the fourth peak specified in requirement α is present, or at least one specific peak selected from the group consisting of the first peak, the second peak, the third peak and the fourth peak is present, and the intensity ratio calculated by the intensity measurement method of at least one of the specific peaks is less than 2.0.
[0773] Furthermore, the lithium-based solid electrolytes obtained in Examples 7 to 13 satisfy the above-mentioned requirement T, requirement X, and requirement Y.
[0774] [Table 5]
[0775]
[0776]
[0777] As shown in the above table, the lithium-based solid electrolyte of the present invention exhibits the desired effects.
[0778] <Example 21>
[0779] A ball mill (P-7 manufactured by Fritsch Japan Co., Ltd.) was used with a pot made of stabilized zirconia (YSZ) (45 ml), grinding balls made of stabilized zirconia (YSZ) (average particle size: 5 mm, weight: 70 g), a rotation speed of 530 rpm, LBO powder (powdered Li 2 B 4 O 7 Li 2 B 4 O 7 (247) powder (manufactured by RARE METALLIC Co., Ltd.) was ball-milled to obtain a lithium compound. The lithium compounds obtained from the plurality of tanks were recovered, 5 g of the recovered lithium compounds were added to water at a powder concentration of 42% by mass, and ultrasonic treatment was performed for 60 minutes to obtain a dispersion A1.
[0780] Next, 2.5 g of LiCl was added to water at a powder concentration of 40% by mass, and ultrasonic treatment was performed for 60 minutes to obtain a solution A2.
[0781] The obtained dispersion A1 and solution A2 were mixed and stirred for 60 minutes using a magnetic stirrer. Next, the obtained dispersion was vacuum dried at 40°C and 10 Pa for 3.5 hours to obtain a powder (lithium-based solid electrolyte). The obtained powder was allowed to stand for a certain period of time in the atmosphere, and the following evaluation was performed in the same manner as in Example 1 in the atmosphere.
[0782] <Examples 22 to 27>
[0783] LiCl was changed to a Li salt described in the table described later, and the contents of each Li salt and water in the obtained lithium-based solid electrolyte were changed to the amounts described in the table described later. A powder of a lithium-based solid electrolyte was obtained in the same manner as in Example 21. After the obtained powder was allowed to stand for a certain period of time in the atmosphere, the following evaluation was performed in the same manner as in Example 1 in the atmosphere.
[0784] In Table 7, the columns "BM-LBO247", "Li salt" and "water" indicate the components in the powder obtained in each example. Specifically, "BM-LBO247" indicates Li salt that has been ball-milled. 2 B 4 O 7 "Li salt" refers to the lithium salt (LiCl, LiI, Li 2 SO 4 The "molar ratio" column in the table shows the relative molar ratio of each component when the molar amount of BM-LBO247 is set to 1.
[0785] Table 7 shows the ion conductivity values of the powder compacts obtained by pressing the lithium-based solid electrolyte obtained in each example at 27°C (room temperature) at an effective pressure of 200 MPa at a measurement temperature of 27°C. The ion conductivity of each powder compact was measured according to the method described in (Ion conductivity measurement (1)) above.
[0786] The water contents in the lithium-based solid electrolytes obtained in Examples 21 to 27 were measured in the same manner as in Examples 1 to 6 and were all 20 to 40% by mass relative to the total mass of the lithium-based solid electrolytes.
[0787] In addition, in the same manner as in Example 5, a powder compact was prepared using the lithium-based solid electrolytes obtained in Examples 21 to 27, and SEM-EDX analysis was performed on the cross section of the obtained powder compact. It was confirmed that a mesh structure was formed in the area where the lithium salt existed.
[0788] In Examples 21 to 27, Li 2 B 4 O 7 The lithium compounds obtained by ball milling the (247) powder (manufactured by RARE METALLIC Co., Ltd.) all satisfy the above-mentioned requirements α, β, γ and δ.
[0789] More specifically, in Examples 21 to 27, Li 2 B 4 O 7 In the Raman spectrum of a lithium compound obtained by ball-milling a (247) powder (manufactured by RARE METALLIC Co., Ltd.), none of the first to third peaks specified in the requirement δ exists.
[0790] Furthermore, in Examples 21 to 27, Li 2 B 4 O 7(247) In the X-ray diffraction pattern of a lithium compound obtained by ball milling a powder (manufactured by RARE METALLIC Co., Ltd.) obtained from X-ray diffraction measurement using CuKα rays, none of the first peak to the fourth peak specified in requirement α is present, or at least one specific peak selected from the group consisting of the first peak, the second peak, the third peak and the fourth peak is present, and the intensity ratio calculated by the intensity measurement method of at least one of the specific peaks is less than 2.0.
[0791] Furthermore, the lithium-based solid electrolytes obtained in Examples 21 to 27 satisfy the above-mentioned requirement T, requirement X, and requirement Y.
[0792] [Table 7]
[0793]
[0794] As shown in the above table, the lithium-based solid electrolyte of the present invention exhibits the desired effects.
[0795] Explanation of symbols
[0796] 1-negative electrode collector, 2-negative electrode active material layer, 3-solid electrolyte layer, 4-positive electrode active material layer, 5-positive electrode collector, 6-working part, 10-all-solid-state lithium-ion secondary battery.
Claims
1. A lithium-based solid electrolyte comprising lithium tetraborate in an amorphous state, water and a lithium salt, wherein: The water content is 45% by mass or less relative to the total mass of the lithium-based solid electrolyte.
2. The lithium-based solid electrolyte according to claim 1, wherein The lithium tetraborate has an OH structure.
3. The lithium-based solid electrolyte according to claim 1, wherein The molar ratio of the content of the lithium salt to the content of the lithium tetraborate is 0.001 to 1.5, The molar ratio of the water content to the lithium tetraborate content is 1 to 12.
4. The lithium-based solid electrolyte according to claim 2, wherein: The lithium salt is a compound represented by formula (1), Formula (1) LiN(R f1 SO2)(R f2 SO2) R f1 and R f2 Each independently represents a fluorine atom or a perfluoroalkyl group.
5. The lithium-based solid electrolyte according to claim 1, wherein When a cross section of a molded body obtained by pressurizing the lithium-based solid electrolyte is observed with a scanning electron microscope, the region where the lithium salt exists exists in a mesh shape.
6. A lithium-based solid electrolyte comprising lithium tetraborate and a lithium salt in an amorphous state, wherein: When a cross section of a molded body obtained by pressurizing the lithium-based solid electrolyte is observed with a scanning electron microscope, the region where the lithium salt exists exists in a mesh shape.
7. The lithium-based solid electrolyte according to claim 6, wherein: The lithium tetraborate has a hydroxyl group.
8. The lithium-based solid electrolyte according to claim 6, wherein The lithium salt is a compound represented by formula (1), Formula (1) LiN(R f1 SO2)(R f2 SO2) R f1 and R f2 Each independently represents a fluorine atom or a perfluoroalkyl group.
9. A method for producing a lithium-based solid electrolyte, which is the method for producing a lithium-based solid electrolyte according to any one of claims 1 to 8, comprising: Step 1, subjecting a lithium-based oxide containing Li and B to mechanical grinding; Step 2, mixing the product obtained in step 1 with water; and Step 3, removing water from the dispersion obtained in step 2 to obtain a lithium-based solid electrolyte, The method for producing the lithium-based solid electrolyte satisfies any one of the following requirements 1 to 3. Requirement 1: The mechanical milling treatment of step 1 is carried out in the presence of a lithium salt containing one or more specific elements, wherein the specific element is selected from the group consisting of F, Cl, Br, I, S, P, Si, Se, Te, C, Sb, As, Sc, Y, Zr, Ti, Hf and N, Requirement 2: In the step 2, the product, water and the lithium salt are mixed, Requirement 3: In the step 3, a product obtained by removing water from the dispersion obtained in the step 2 and the lithium salt are mixed to obtain the lithium-based solid electrolyte.
10. The method for producing a lithium-based solid electrolyte according to claim 9, wherein: In the step 3, the dispersion obtained in the step 2 is dried under the conditions of 20 Pa or less and 40° C. or less, thereby obtaining a lithium-based solid electrolyte.
11. The method for producing a lithium-based solid electrolyte according to claim 9, which satisfies the requirement 1, and Prior to the step 1, the method further includes a step 0 of mechanically grinding the lithium-based oxide containing Li and B in an environment in which the lithium salt is not present.
12. A modified positive electrode active material, comprising a positive electrode active material and a coating layer disposed on the positive electrode active material, wherein: The coating layer comprises the lithium-based solid electrolyte according to any one of claims 1 to 8.
13. A modified negative electrode active material, comprising a negative electrode active material and a coating layer disposed on the negative electrode active material, wherein: The coating layer comprises the lithium-based solid electrolyte according to any one of claims 1 to 8.
14. An all-solid-state secondary battery, comprising, in sequence, a positive electrode active material layer, a solid electrolyte layer, and a negative electrode active material layer, wherein: At least one of the positive electrode active material layer, the solid electrolyte layer, and the negative electrode active material layer includes the lithium-based solid electrolyte according to any one of claims 1 to 8. 15 . An electrode sheet for an all-solid-state secondary battery, comprising the lithium-based solid electrolyte according to claim 1 . 16 . A solid electrolyte sheet comprising the lithium-based solid electrolyte according to claim 1 .
17. An electrode for an all-solid-state secondary battery, comprising: An active material layer comprising an active material and a lithium-based solid electrolyte as claimed in any one of claims 1 to 8; and Current collector.
Citation Information
Patent Citations
Latex agglutination reaction measuring instrument
JP1987022066A
Catalyst carrier and production thereof
JP1990006856A
Four-wheel steering device
JP1991045473A
Distortion compensator
JP1993090844A
Assignment decision support system
JP1994004516A